Genome sequencing and multi-stage, blood-feeding, and tissue-specific transcriptome atlas of the Rocky Mountain wood tick provide a critical resource for this vector - Joshua E. Tompkin; Perot Saelao; Justyna Kruczalak; Huiqing Yeo; Pia U. Olafson; Sheina B. Sim; Kennan Oyen; Melissa Kelley; Renee L. Corpuz; Brian Scheffler; Scott M. Geib; Anna K. Childers; et al. (Insect Biochemistry and Molecular Biology, 2026)

Agricultural practices shape beetle communities in field margins directly and through indirect effects driven by plants - Léa Genty; Guillaume Fried; Benoit Penel; Cyril Marty; Axel Bourdonné; Julien Haran; Gael J. Kergoat; Laure Benoit; Anne-Laure Clamens; Christine N. Meynard (Agriculture, Ecosystems & Environment, 2026)

Genomic insights into the evolutionary history and cryptic diversity of two-toed sloths (Choloepus) in Amazonia - Larissa S. Arantes; Luísa S. Marins; Linda Hagberg; Radarane Santos Sena; Benoit de Thoisy; Marta Svartman; Mariluce Rezende Messias; Cláudia R. Silva; Nicole M. Foley; William J. Murphy; Camila C. Ribas; Fabrício R. Santos; et al. (Molecular Phylogenetics and Evolution, 2026)

Harnessing wine yeasts: Unveiling their potential as lipid supplements - Julian J. Pietersen; Stéphanie Rollero; Benoit Divol (International Journal of Food Microbiology, 2026)

Acoustic evidence for topographic blocking on a steep submarine canyon wall - Astrid B. Leitner; Chad M. Waluk; Kim R. Reisenbichler; Rob E. Sherlock; Bruce H. Robison; Kelly J. Benoit‐Bird (Limnology and Oceanography, 2026)
Diel vertical migration (DVM) is the largest mass‐movement of animals on Earth, with profound ecological and biogeochemical consequences. DVM has mostly been studied in the open ocean; however, at steep slopes, pelagic animals including vertical migrators must contend with the seafloor, emphasizing the importance of understanding DVM in these prevalent, critical habitats. Here we used active acoustics in combination with video to conduct a detailed study of the interactions of vertical migrators with the steep wall of a submarine canyon during their sunrise descent. We found regular and frequent, high‐density sunrise aggregations of animals consistent with seafloor blocking of descending vertical migrators across all seasons. While topographic blocking was thought to be primarily caused by nighttime advection of migrators over shallows by prevailing currents, here the occurrence of this phenomenon was observed to be largely independent of oceanographic drivers including advection as measured by an ADCP, providing evidence that behavior plays an important role. Advection, season, upwelling, and other environmental factors were found to impact specific characteristics of sunrise aggregations but not likelihood of occurrence. Given its intensity and prevalence, topographic blocking likely creates high‐quality, predictable foraging opportunities for a large diversity of predators and influences the abundance and habitat use of predators in the area. The steep slopes of this canyon, as with any abrupt bathymetry, juxtapose the deep and the shallow, the benthic and the pelagic, and the offshore and nearshore. Thus, topographic blocking may be prevalent in other steep canyons and at steep bathymetry more generally.

Resource variability shapes the ecology of social information and collective sensing - William K. Oestreich; Jenna E. Kohles; Briana Abrahms; Kelly J. Benoit-Bird; Andrew M. Berdahl; John P. Ryan; Dina K.N. Dechmann (Trends in Ecology & Evolution, 2026)

Beetle communities in agricultural landscapes: relative influences of climate, landscape, plant communities and agricultural practices - B. Penel; L. Genty; C. Marty; A. Bourdonné; A.-L. Clamens; L. Benoit; L. Soldati; A. Migeon; G.J. Kergoat; J. Haran; G. Fried; C.N. Meynard (Agriculture, Ecosystems & Environment, 2026)

Petrophysics and mass balance integration for alteration detection in orogenic gold exploration - Yasaman Nemati; J. Christian Dupuis; Benoit Quesnel; Bernard Giroux; Richard Smith; Georges Beaudoin (Journal of Applied Geophysics, 2026)

Circadian modulation of core temperature and thermoregulatory strain during live-fire compartment exposure in firefighters - Benoit Mauvieux; Adrian Markov; Stéphane Besnard; Yvan Touitou; Ben J. Edwards (Journal of Thermal Biology, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Habitat suitability model for identifying human-wildlife interface and implications for wildlife trade of Sunda pangolin in Borneo - Chrishen R. Gomez; Caroline C. Sartor; David W. Macdonald; Paul J. Johnson; Benoit Goossens; Elisa Panjang; Penny C. Gardner; Nicola K. Abram; Roshan Guharajan; Seth T. Wong; Jaffly Jubili; Jasrin Kuntagil; et al. (Environmental Monitoring and Assessment, 2026)
Pangolins are the most trafficked mammals in the world. Sunda pangolins ( Manis javanica ), in particular, are critically endangered due to their proximity to consumption hotspots and the scale of the globalized illegal trade network. Data on their ecological drivers can inform targeted strategies to cauterize supply lines. We used data from 1455 camera-stations deployed between 2008 and 2024 across a heterogeneous mix of landscapes in Sabah, northern Borneo, to model the geomorphological and anthropogenic drivers of Sunda pangolin distribution. Our most parsimonious logistic regression model included six variables: accessibility to human population ( β = 0.597, p = 0.004), soil cation exchange capacity ( β = −0.665, p = 0.003), soil clay content ( β = −0.311, p = 0.051), soil nitrogen concentration ( β = 0.9862, p = 0.0001), soil bulk density ( β = 0.43, p = 0.143), and topographic position index ( β = −0.61, p = 0.005). The model performed well as evaluated using an out-of-sample test dataset (sensitivity = 0.89, specificity = 0.57, and AUC = 0.73). A high proportion (~ 43%) of rural, human-dominated areas were identified as highly suitable pangolin habitat, but only ~ 15% of these areas are protected. We further confirmed the overlap in highly suitable pangolin habitat and human-occupied land using an independent citizen science dataset of pangolin detections collected between 2019 and 2024 (Boyce index = 0.75). Our results illustrate that Sunda pangolins often live in high-risk areas but also suggest an opportunity to develop community-centered conservation strategies to curb poaching and cauterize supply lines fueling the trade of Sunda pangolins in Southeast Asia.

Regimes of bedforms created by down-slope density currents - Octavio E. Sequeiros; Benoit Spinewine; Gary Parker; Carlos Pirmez; Enrica Viparelli; Juan J. Fedele; Marcelo H. García; Débora Koller; Michele Bolla Pittaluga; Miwa Yokokawa (Earth-Science Reviews, 2026)

Paleontological Knowledge among the Basotho and San of Lesotho: A Review Including Insights from Paul Ellenberger’s Archives - J. Benoit; C. Helm; E.M. Bordy (Geoheritage, 2025)
Paul Ellenberger’s archives provide insight into the Basotho and San peoples palaeontological knowledge in southern Africa, specifically from Lesotho. For instance, it preserves many published and unpublished accounts of Basotho people discovering dinosaur footprints and bones in Lesotho. Moreover, the Basotho folk tale (a “litsomo” in Sesotho) featuring the voracious monster Kholumolumo is here demonstrably linked to dinosaur trace and bone fossils in the main Karoo Basin of southern Africa, suggesting that this well-known local fable functions as a geomyth. For the San, Ellenberger hypothesised that their understanding of fossil footprints reflected a grasp of geoscientific concepts, potentially including the principles of superposition, faunal succession, locomotor biology, and plate tectonics. He connected the San myths of the Agama (!Khau) and All-Devourer (//Khwai-hemm) to fossil footprints, arguing in an unpublished manuscript that the San narrative indicated a historical awareness of not only the fossil track record but also of geoscientific concepts. Despite Ellenberger’s intriguing interpretations, the evidence for this San geomyth is tenuous. It is possible that this geomyth may partly result from Ellenberger’s enthusiasm for linking indigenous knowledge with his interests in fossil footprints. The evidence for San understanding of geological concepts remains speculative, and more robust data is needed to substantiate these claims. Nevertheless, this review paper highlights the scientific contributions of indigenous populations as an early form of citizen science and underscore the complex interactions between indigenous knowledge and scientific inquiry.

Atlantic-wide connectivity of Ascension Island green turtles revealed by finer-scale mitochondrial DNA markers - Sophia A. Coveney; Eva Jiménez-Guri; Samantha Ball; Nathalie Mianseko; Annette C. Broderick; Brendan J. Godley; Joana M. Hancock; Welton Quirino Pereira; Aissa Regalla; Rita Gomes Rocha; Cheibani Senhoury; Benoit de Thoisy; et al. (Conservation Genetics, 2025)
Marine turtles undertake long migrations across different geographies and habitats, exposing them to a wide range of threats throughout their lifespan. Analysing population structure and connectivity is key to informing effective conservation management. We expand knowledge of Atlantic-wide connectivity of green turtles ( Chelonia mydas ) by characterising the genetic structure of the Ascension Island nesting population, one of the largest in the Atlantic Ocean, and carrying out Atlantic population structure and mixed stock analyses using high-resolution genetic markers. We amplified a ~ 738 bp fragment (extended D-loop) and a highly polymorphic mitochondrial short tandem repeat (mtSTR) fragment of the mitochondrial DNA control region, designating haplotypes based on (1) extended D-loop and (2) the extended D-loop and mtSTR combined. Overall, 11 extended D-loop and 33 combined haplotypes were found, the dominant haplotypes being CM-A8.1 and CM-A8.1/7-12-4-4. Population structure analysis found three main genetic groups: Northwest Atlantic, Northern South America, and South and East Atlantic. Mixed stock analyses indicate Ascension Island as a major source for juvenile foraging aggregations in the Southwest Atlantic (34–55%) and Central Africa (18–78%), with some contribution to West Africa (3–20%). Green turtles are vulnerable to fishery bycatch in the coastal waters of the South and East Atlantic. Our study underlines how improving sample sizes of Atlantic mtSTR haplotypes could further elucidate green turtle connectivity across threatened regions. We urge international collaboration to minimise mtSTR data gaps, in order to enhance connectivity assessments and improve conservation measures between countries that share populations.

Seagrasses under stress: Independent negative effects of elevated temperature and light reduction at multiple levels of organization - Alissa V. Bass; Laura J. Falkenberg; Benoit Thibodeau (Limnology and Oceanography, 2025)
Seagrasses are important foundation species, which support coastal biodiversity and provide socioeconomic benefits. However, seagrasses are threatened by anthropogenic changes, including the elevated temperature associated with marine heatwaves (MHWs) and light limitation from eutrophication or increased sedimentation. In this experiment, we exposed the seagrass Halophila ovalis to 10‐d of elevated temperature, simulating a MHW, and three light intensities to examine the impacts on multiple levels of organization, that is, growth, productivity, nitrogen cycling, and leaf microbiome. We found that both the MHW temperature and decreased light independently negatively impacted seagrass growth of new leaves, with decreased light also reducing new leaf area and rhizome elongation rate, and the occurrence of MHW temperatures increasing the rate of leaf loss. Similarly, chlorophyll concentration was altered by both stressors independently, with a common response to reduced light (increased chlorophyll concentration) significantly lower under the MHW temperature. Nitrogen assimilation rate into the leaves also decreased under both MHW temperature and reduced light availability. The leaf microbiome shifted in response to the MHW temperature and lower light, with these conditions prompting relatively more anaerobic microbes but less oxidative stress‐tolerant bacteria, and less prokaryotes performing phototrophy and (oxygenic) photoautotrophy. In conclusion, we show elevated temperature representing a MHW and light limitation can drive decreased seagrass growth, chlorophyll concentration, and cause shifts in leaf microbial functional groups, although there was little interaction between stressors. It is therefore important that good water clarity and habitat health is maintained to reduce the susceptibility of seagrasses to extreme climatic events.

Methanol on red TNOs: A link between early composition and irradiation history - E. Hénault; D. Baklouti; R. Brunetto; Z. Djouadi; R.G. Urso; P. Benoit-Lamaitrie; J. Bourçois; O. Mivumbi; C.M. Dalle Ore; A. Ricca (Icarus, 2025)

Role of viral coinfection in post-pandemic invasive Group A streptococcal infections in adults, a nation-wide cohort study (iGASWISS) - S. Musumeci; A. MacPhail; M. Weisser Rohacek; A. Erba; D. Goldenberger; C. Lang; E. Colin-Benoit; S. L. Leib; P. Sendi; C. Chuard; V. Erard; C. Fournier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Objective During the winter season of 2022–2023, numerous countries experienced a surge in invasive Streptococcus pyogenes (iGAS) infections. The role of viral coinfections in the post-COVID surge has not been elucidated. We report nation-wide data describing clinical presentation, microbiological characteristics, and associations with viral infection in adults during this period. Methods A multicenter retrospective cohort study was conducted across 10 hospitals in Switzerland, including adults (> 16 years old) with iGAS infection from November 2022 to February 2023. Descriptive analysis was performed. A multivariable logistic regression model was fitted to assess the impact of viral coinfection. In addition, genetic analysis was performed in available isolates. Results A total of 194 patients were included, with a median age of 50 years (interquartile range [IQR]: 37–69). 17/194 (8.8%) were immunosuppressed and 40/194 (20.6%) exhibited concomitant viral infections, predominantly Influenza A (21/40, 53%). Illness severity was high: 65/194 (33.5%) of cases necessitated admission to an intensive care unit (ICU), and the 30-day mortality was 4% ( n = 8). Among the available strains for genetic analysis ( n = 48), heterogeneity was found although ST28- emm 1 isolates (also known as M1UK) was predominant (22/48). Conclusion The post-COVID iGAS surge in Switzerland was associated with high levels of morbidity and mortality in immunocompetent adults. M1UK was predominant within the iGAS strains circulating in Switzerland during the study period and viral coinfection was a predictor for ICU admission and mortality.

Plant Trait Matching Occurs in Facilitative Interactions Across Global Drylands - Imke C. Smit; Peter C. le Roux; Santiago Soliveres; Nicolas Gross; Yoann Le Bagousse‐Pinguet; Hugo Saiz; Mehdi Abedi; Rodrigo Ahumada; Antonio I. Arroyo; Sergio Asensio; Richard Benoit; Niels Blaum; et al. (Global Ecology and Biogeography, 2025)
Aim Plant functional traits can influence interaction outcomes between nurse and target plants through a “functional trait match”, which occurs when the traits of nurse plants ameliorate their environment, and target plants possess traits that allow them to benefit from this ameliorated environment. We investigated how the traits of putative nurse species affect interaction outcomes across global drylands and determined the functional match that promotes facilitation. We also investigated how grazing pressure and global climatic and edaphic gradients affected this trait match. Location Global drylands. Time Period 2016–2019. Major Taxa Studied Vascular plants. Methods We used a collaborative survey conducted across 29 sites from five continents, where we gathered in situ co‐occurrences of dominant species (‘nurses’) and other vascular plant species, as well as their functional traits [plant height and leaf dry matter content (LDMC)]. Climate, edaphic variables and grazing pressure were measured in situ or extracted from databases. We used a model building approach to determine the effect of dominant plant traits on interaction outcomes, and how the functional trait match between nurse and target species is affected by environmental variables. Results Tall dominant plants with conservative leaves generally had a greater positive effect on species richness and cover beneath their canopies, but these effects were strongly modulated by grazing pressure and soil pH. Target plants that were significantly associated with dominant plants tended to be shorter, and have more acquisitive leaves than dominant plants, regardless of environmental conditions. However, the difference in height and LDMC between dominant plants and negatively associated target plants was strongly affected by environmental conditions. Main Conclusions Functional traits play a significant role in determining interaction outcomes between dryland plants. Facilitation in drylands is driven by a conservative‐acquisitive trait match, a pattern observed regardless of grazing pressure, climate and soil conditions.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Late 21st‐Century Climate and Land Use Driven Loss of Plant Diversity in African Mountains - João de Deus Vidal Junior; Alexandre Antonelli; Clinton Carbutt; Vincent Ralph Clark; Tobias Fremout; Christopher Chapano; Inês Chelene; David Chuba; Tadesse Woldemariam Gole; Clayton Langa; Benoit Loeuille; Ermias Lulekal Molla; et al. (Global Change Biology, 2025)
With the 1.5°C–5°C increase in global temperature projected for this century, many plant species are expected to shift their distribution ranges to track their environmental requirements. Across several mountain regions, responses to climate change like upslope shifts may result in accelerated rates of species turnover, species richness increases in upper montane belts, and amplified habitat losses. Yet, evidence of how such processes may influence plant diversity in Africa is still scarce. Here, using a species distribution modeling approach, we quantify and map how different scenarios of climatic and land‐use changes may affect plant species ranges in African mountains. Using individually tuned models and dispersal buffers, we compared distribution losses and potential expansion through dispersal across 607 vascular plant species under three shared socioeconomic pathways for the end of the century. Our projections indicate that keeping warming under 2°C until 2100 under a sustainability scenario (SSP1.26), almost half (49.3%) of the species would experience a contraction in suitable areas, compared to 71%–75.6% in case these targets are not met (SSP3.70 and SSP5.85). Among these losses, mean contractions between 19% and 50.4% are predicted depending on the scenario. We project rates of upslope shifts that may be up to three times higher than the global calculated average. Contractions will be higher for species occurring at upper elevations, and trees and shrubs will show lower declines. Our findings align with previously reported trends of upslope shifts of species distributions but suggest that accelerated rates of change may limit the capacity of some species to track their niche based solely on their natural dispersal capacity. This implies that further efforts to improve habitat connectivity, restoration, and assisted migration may be necessary.

Skeletal accumulations of the parareptile Procolophon trigoniceps reflect fossorial response to Early Triassic climatic instability across southern Gondwana - Roger M.H. Smith; Frederik P. Wolvaardt; Juan C. Cisneros; Felipe L. Pinheiro; Joseph J. Bevitt; Julien Benoit (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

The African Dragon Stones: Geomyths About Snakes and the Origin of Diamonds in South Africa - J. Benoit (Geoheritage, 2025)
Geomyths of snakes guarding treasures or bearing head gems are widespread in Eurasia and the northern half of Africa, but are rare in sub-saharan Africa. This contribution reports the earliest written evidence of the existence of versions of this geomyth in at least two cultures: the IsiXhosa and San indigenous inhabitants of South Africa. The myths are about the origin of diamonds, and how snakes were believed to be the creator of diamonds and carried the precious gem on their head. These would have accounted for the diamond rush in southern Africa in the late 1800s. It is possible that these geomyths in southern Africa resulted from the mixing between local folklore and the Dragon stone myths imported from Eurasia. The possibility that the South African versions of the myth may be related to vertebrate fossils (with braincase infilled with crystals) is also discussed.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

ACE-Net: A-line coordinates encoding network for vascular structure segmentation in ultrasound images - Beatriz Farola Barata; Guiqiu Liao; Gianni Borghesan; Keir McCutcheon; Johan Bennett; Benoit Rosa; Michel de Mathelin; Florent Nageotte; Michalina J. Gora; Jos Vander Sloten; Emmanuel Vander Poorten; Diego Dall’Alba (Medical & Biological Engineering & Computing, 2025)
Ultrasound (US) imaging enables the evaluation of vascular structures in real time, and it can provide morphological and pathological information during US-guided procedures. Automatic prediction of vascular structure boundaries can help clinicians in locating and measuring target structures more accurately and efficiently. Most existing US segmentation methods use per-pixel classification or regression, which require post-processing to obtain contour coordinates. In this work, we present ACE-Net, a novel approach that directly predicts the contour coordinates for every scanning line (A-line) in US images. ACE-Net combines two main modules: a boundary regression module that predicts the upper and lower coordinates of the target area for each A-line, and an A-line classification module that determines whether an A-line belongs to the target area or not. We evaluated our method on three clinical US datasets using, among others, dice similarity coefficient (DSC) and inference time as performance metrics. Our method outperformed state-of-the-art segmentation methods in inference time while achieving superior or comparable performance in DSC. ACE-Net is publicly available at https://github.com/bfarolabarata/ace-net . Graphical abstract ACE-Net is a deep CNN architecture designed for direct contour segmentation of vascular structures in ultrasound images. It formulates segmentation as a boundary regression process combined with the prediction of vascular structure presence. To achieve this, ACE-Net introduces an A-line-based encoding scheme, representing contour coordinates of each vascular structure as two boundary vectors (upper and lower). The network consists of a backbone module, an A-line feature extractor, a multi-scale fusion module, and two final head encoders, which output boundary coordinates and presence probabilities. By leveraging a presence vector, ACE-Net enhances segmentation accuracy and effectively handles common ultrasound artifacts without requiring pre-processing. Its architecture is specifically designed to address the imbalance between lateral and axial information in ultrasound images, and it enables real-time clinical metric computation.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Dynamic energy budget modelling of anuran metamorphosis - Carlo Romoli; Benoit Goussen; Lennart Weltje; Pernille Thorbek; Douglas J. Fort; Brittanie F. Peake; Joachim Kleinmann; Erik B. Muller (Ecological Modelling, 2025)

CanESM5-derived ocean wave projections — Considerations for coarse resolution climate models - Mercè Casas-Prat; Leah Cicon; Benoit Pouliot; Natacha B. Bernier; Alex J. Cannon; Rodney Chan (Ocean Modelling, 2024)

Observational Assessment of Changes in Earth’s Energy Imbalance Since 2000 - Norman G. Loeb; Seung-Hee Ham; Richard P. Allan; Tyler J. Thorsen; Benoit Meyssignac; Seiji Kato; Gregory C. Johnson; John M. Lyman (Surveys in Geophysics, 2024)
Satellite observations from the Clouds and the Earth’s Radiant Energy System show that Earth’s energy imbalance has doubled from 0.5 ± 0.2 Wm −2 during the first 10 years of this century to 1.0 ± 0.2 Wm − 2 during the past decade. The increase is the result of a 0.9 ± 0.3 Wm −2 increase absorbed solar radiation (ASR) that is partially offset by a 0.4 ± 0.25 Wm −2 increase in outgoing longwave radiation (OLR). Despite marked differences in ASR and OLR trends during the hiatus (2000–2010), transition-to-El Niño (2010–2016) and post-El Niño (2016–2022) periods, trends in net top-of-atmosphere flux (NET) remain within 0.1 Wm −2 per decade of one another, implying a steady acceleration of climate warming. Northern and southern hemisphere trends in NET are consistent to 0.06 ± 0.31 Wm −2 per decade due to a compensation between weak ASR and OLR hemispheric trend differences of opposite sign. We find that large decreases in stratocumulus and middle clouds over the sub-tropics and decreases in low and middle clouds at mid-latitudes are the primary reasons for increasing ASR trends in the northern hemisphere (NH). These changes are especially large over the eastern and northern Pacific Ocean, and coincide with large increases in sea-surface temperature (SST). The decrease in cloud fraction and higher SSTs over the NH sub-tropics lead to a significant increase in OLR from cloud-free regions, which partially compensate for the NH ASR increase. Decreases in middle cloud reflection and a weaker reduction in low-cloud reflection account for the increase in ASR in the southern hemisphere, while OLR changes are weak. Changes in cloud cover in response to SST increases imply a feedback to climate change yet a contribution from radiative forcing or internal variability cannot be ruled out.

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Re-assessing the age of the type locality of Nythosaurus larvatus (Therapsida, Cynodontia) and implications on the evolutionary dynamics of cynodonts - J. Benoit; S. Jirah; E.S. Lund; T. Lafferty; V. Buffa; L.A. Norton (Proceedings of the Geologists' Association, 2024)

Invertebrate and dinoflagellate marine toxins targeting signaling and key components of the skeletal neuromuscular system of vertebrates - Jordi Molgó; Aurélie Couesnon; Evelyne Benoit; Armen Zakarian; Denis Servent; J. Cesar Cardenas; Frédéric A. Meunier (Toxicon, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Smart soils track the formation of pH gradients across the rhizosphere - Daniel Patko; Qizhi Yang; Yangminghao Liu; Panagiotis Falireas; Benoit Briou; Bhausaheb V. Tawade; Timothy S. George; Tim J. Daniell; Michael P. MacDonald; Vincent Ladmiral; Bruno Ameduri; Lionel X. Dupuy (Plant and Soil, 2024)
Aims Our understanding of the rhizosphere is limited by the lack of techniques for in situ live microscopy. Current techniques are either destructive or unsuitable for observing chemical changes within the pore space. To address this limitation, we have developed artificial substrates, termed smart soils, that enable the acquisition and 3D reconstruction of chemical sensors attached to soil particles. Methods The transparency of smart soils was achieved using polymer particles with refractive index matching that of water. The surface of the particles was modified both to retain water and act as a local sensor to report on pore space pH via fluorescence emissions. Multispectral signals were acquired from the particles using a light sheet microscope, and machine learning algorithms predicted the changes and spatial distribution in pH at the surface of the smart soil particles. Results The technique was able to predict pH live and in situ within ± 0.5 units of the true pH value. pH distribution could be reconstructed across a volume of several cubic centimetres around plant roots at 10 μm resolution. Using smart soils of different composition, we revealed how root exudation and pore structure create variability in chemical properties. Conclusion Smart soils captured the pH gradients forming around a growing plant root. Future developments of the technology could include the fine tuning of soil physicochemical properties, the addition of chemical sensors and improved data processing. Hence, this technology could play a critical role in advancing our understanding of complex rhizosphere processes.

Tectono-sedimentary evolution of the Suriname margin in the cretaceous: A sequence-stratigraphic framework - V. Delhaye-Prat; Julien Bourget; Gwladys Gaillot; Jérémie Gaillot; François Sapin; Charlotte Fillon; Jing Ye; Tim Wright; Anne-Claire Chaboureau; Nicoletta Buratti; Benoit Magnier; Andrei Belopolsky; et al. (Earth-Science Reviews, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Linking biodiversity, ecosystem function, and Nature’s contributions to people: a macroecological energy flux perspective - Ana Carolina Antunes; Emilio Berti; Ulrich Brose; Myriam R. Hirt; Dirk N. Karger; Louise M.J. O’Connor; Laura J. Pollock; Wilfried Thuiller; Benoit Gauzens (Trends in Ecology & Evolution, 2024)

Modelling the occupancy of two bird species of conservation concern in a managed Acadian Forest landscape: Applications for forest management - Remus James; Joseph R. Bennett; Scott Wilson; Greg Adams; Ken McIlwrick; Marc J. Mazerolle; Emily Smenderovac; Kelly Honeyman; Tom Swystun; Benoit Hamel; Lisa A. Venier (Forest Ecology and Management, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Brain metabolite levels in remitted psychotic depression with consideration of effects of antipsychotic medication - Hideaki Tani; Iska Moxon-Emre; Natalie J. Forde; Nicholas H. Neufeld; Kathleen S. Bingham; Ellen M. Whyte; Barnett S. Meyers; George S. Alexopoulos; Matthew J. Hoptman; Anthony J. Rothschild; Hiroyuki Uchida; Alastair J. Flint; et al. (Brain Imaging and Behavior, 2023)
Background The neurobiology of psychotic depression is not well understood and can be confounded by antipsychotics. Magnetic resonance spectroscopy (MRS) is an ideal tool to measure brain metabolites non-invasively. We cross-sectionally assessed brain metabolites in patients with remitted psychotic depression and controls. We also longitudinally assessed the effects of olanzapine versus placebo on brain metabolites. Methods Following remission, patients with psychotic depression were randomized to continue sertraline + olanzapine ( n = 15) or switched to sertraline + placebo ( n = 18), at which point they completed an MRS scan. Patients completed a second scan either 36 weeks later, relapse, or discontinuation. Where water-scaled metabolite levels were obtained and a Point-RESolved Spectroscopy sequence was utilized, choline, myo-inositol, glutamate + glutamine (Glx), N -acetylaspartate, and creatine were measured in the left dorsolateral prefrontal cortex (L-DLPFC) and dorsal anterior cingulate cortex (dACC). An ANCOVA was used to compare metabolites between patients ( n = 40) and controls ( n = 46). A linear mixed-model was used to compare olanzapine versus placebo groups. Results Cross-sectionally, patients (compared to controls) had higher myo-inositol (standardized mean difference [SMD] = 0.84; 95%CI = 0.25–1.44; p = 0.005) in the dACC but not different Glx, choline, N -acetylaspartate, and creatine. Longitudinally, patients randomized to placebo (compared to olanzapine) showed a significantly greater change with a reduction of creatine (SMD = 1.51; 95%CI = 0.71–2.31; p = 0.0002) in the dACC but not glutamate + glutamine, choline, myo-inositol, and N -acetylaspartate. Conclusions Patients with remitted psychotic depression have higher myo-inositol than controls. Olanzapine may maintain creatine levels. Future studies are needed to further disentangle the mechanisms of action of olanzapine.

Technological innovations to reduce the impact of bottom gears on the seabed - Antonello Sala; Jochen Depestele; Aysun Gümüş; Pascal Laffargue; J. Rasmus Nielsen; Hans Polet; Chris J. Smith; Mustafa Zengin; Francois Bastardie; Ole R. Eigaard; Katell G. Hamon; Frank Jensen; et al. (Marine Policy, 2023)

Redesigning crop varieties to win the race between climate change and food security - Kevin V. Pixley; Jill E. Cairns; Santiago Lopez-Ridaura; Chris O. Ojiewo; Maryam Abba Dawud; Inoussa Drabo; Taye Mindaye; Baloua Nebie; Godfrey Asea; Biswanath Das; Happy Daudi; Haile Desmae; et al. (Molecular Plant, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Corrigendum: Ten lessons on the resilience of the EU common fisheries policy towards climate change and fuel efficiency - A call for adaptive, flexible and well-informed fisheries management - Francois Bastardie; David A. Feary; Thomas Brunel; Laurence T. Kell; Ralf Döring; Sebastien Metz; Ole R. Eigaard; Oihane C. Basurko; Valerio Bartolino; Jacob Bentley; Benoit Berges; Sieme Bossier; et al. (Frontiers in Marine Science, 2023)

PERMANOVA testing and Poisson Log-Normal modelling unravel how two traditional cheeses are distinguished through sorting and verbalization tasks - P.-M. Grollemund; L. Lenoir; J. Benoit; C. Chassard; C. Bord (Food Quality and Preference, 2023)

Evidence of backcross inviability and mitochondrial DNA paternal leakage in sea turtle hybrids - Sibelle T. Vilaça; Francesco Maroso; Paulo Lara; Benoit de Thoisy; Damien Chevallier; Larissa Souza Arantes; Fabricio R. Santos; Giorgio Bertorelle; Camila J. Mazzoni (Molecular Ecology, 2023)
Hybridization is known to be part of many species' evolutionary history. Sea turtles have a fascinating hybridization system in which species separated by as much as 43 million years are still capable of hybridizing. Indeed, the largest nesting populations in Brazil of loggerheads ( Caretta caretta ) and hawksbills ( Eretmochelys imbricata ) have a high incidence of hybrids between these two species. A third species, olive ridleys ( Lepidochelys olivacea ), is also known to hybridize although at a smaller scale. Here, we used restriction site‐associated DNA sequencing (RAD‐Seq) markers, mitogenomes, and satellite‐telemetry to investigate the patterns of hybridization and introgression in the Brazilian sea turtle population and their relationship with the migratory behaviours between feeding and nesting aggregations. We also explicitly test if the mixing of two divergent genomes in sea turtle hybrids causes mitochondrial paternal leakage. We developed a new species‐specific PCR‐assay capable of detecting mitochondrial DNA (mtDNA) inheritance from both parental species and performed ultra‐deep sequencing to estimate the abundance of each mtDNA type. Our results show that all adult hybrids are first generation (F1) and most display a loggerhead migratory behaviour. We detected paternal leakage in F1 hybrids and different proportions of mitochondria from maternal and paternal species. Although previous studies showed no significant fitness decrease in hatchlings, our results support genetically‐related hybrid breakdown possibly caused by cytonuclear incompatibility. Further research on hybrids from other populations in addition to Brazil and between different species will show if backcross inviability and mitochondrial paternal leakage is observed across sea turtle species.

Determinants of sun bear Helarctos malayanus habitat use in Sabah, Malaysian Borneo and its predicted distribution under future forest degradation and loss - Roshan Guharajan; Jesse F. Abrams; Nicola K. Abram; Hong Ye Lim; Gopalasamy Reuben Clements; Nicolas J. Deere; Matthew J. Struebig; Benoit Goossens; Penny C. Gardner; Jedediah F. Brodie; Alys Granados; Shu Woan Teoh; et al. (Biodiversity and Conservation, 2023)

Towards a genetic theory of island biogeography: Inferring processes from multidimensional community‐scale data - Isaac Overcast; Guillaume Achaz; Robin Aguilée; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Evan P. Economo; Rampal S. Etienne; Rosemary Gillespie; Claire Jacquet; Flora Jay; Susan Kennedy; et al. (Global Ecology and Biogeography, 2023)
Background MacArthur and Wilson's theory of island biogeography has been a foundation for obtaining testable predictions from models of community assembly and for developing models that integrate across scales and disciplines. Historically, however, these developments have focused on integration across ecological and macroevolutionary scales and on predicting patterns of species richness, abundance distributions, trait data and/or phylogenies. The distribution of genetic variation across species within a community is an emerging pattern that contains signatures of past population histories, which might provide an historical lens for the study of contemporary communities. As intraspecific genetic diversity data become increasingly available at the scale of entire communities, there is an opportunity to integrate microevolutionary processes into our models, moving towards development of a genetic theory of island biogeography. Motivation/goal We aim to promote the development of process‐based biodiversity models that predict community genetic diversity patterns together with other community‐scale patterns. To this end, we review models of ecological, microevolutionary and macroevolutionary processes that are best suited to the creation of unified models, and the patterns that these predict. We then discuss ongoing and potential future efforts to unify models operating at different organizational levels, with the goal of predicting multidimensional community‐scale data including a genetic component. Main conclusions Our review of the literature shows that despite recent efforts, further methodological developments are needed, not only to incorporate the genetic component into existing island biogeography models, but also to unify processes across scales of biological organization. To catalyse these developments, we outline two potential ways forward, adopting either a top‐down or a bottom‐up approach. Finally, we highlight key ecological and evolutionary questions that might be addressed by unified models including a genetic component and establish hypotheses about how processes across scales might impact patterns of community genetic diversity.

G﻿lobal phylogeography of ridley sea turtles (Lepidochelys spp.): evolution, demography, connectivity, and conservation - Sibelle Torres Vilaça; Anelise Torres Hahn; Eugenia Naro-Maciel; F. Alberto Abreu-Grobois; Brian W. Bowen; Jaqueline C. Castilhos; Claudio Ciofi; Nancy N. FitzSimmons; Michael P. Jensen; Angela Formia; Colin J. Limpus; Chiara Natali; et al. (Conservation Genetics, 2022)
Globally distributed marine taxa are well suited for investigations of biogeographic impacts on genetic diversity, connectivity, and population demography. The sea turtle genus Lepidochelys includes the wide-ranging and abundant olive ridley ( L. olivacea ), and the geographically restricted and ‘Critically Endangered’ Kemp’s ridley ( L. kempii ). To investigate their historical biogeography, we analyzed a large dataset of mitochondrial DNA (mtDNA) sequences from olive (n = 943) and Kemp’s (n = 287) ridleys, and genotyped 15 nuclear microsatellite loci in a global sample of olive ridleys (n = 285). We found that the ridley species split ~ 7.5 million years ago, before the Panama Isthmus closure. The most ancient mitochondrial olive ridley lineage, located in the Indian Ocean, was dated to ~ 2.2 Mya. Both mitochondrial and nuclear markers revealed significant structure for olive ridleys between Atlantic (ATL), East Pacific (EP), and Indo-West Pacific (IWP) areas. However, the divergence of mtDNA clades was very recent (< 1 Mya) with low within- clade diversity, supporting a recurrent extinction-recolonization model for these ocean regions. All data showed that ATL and IWP groups were more closely related than those in the EP, with mtDNA data supporting recent recolonization of the ATL from the IWP. Individual olive ridley dispersal between the ATL, EP, and IN/IWP could be interpreted as more male- than female-biased, and genetic diversity was lowest in the Atlantic Ocean. All populations showed signs of recent expansion, and estimated time frames were concordant with their recent colonization history. Investigating species abundance and distribution changes over time is central to evolutionary biology, and this study provides a historical biogeographic context for marine vertebrate conservation and management.

Late Cenozoic environmental changes drove the diversification of a weevil genus endemic to the Cape Floristic Region - Noémie M.‐C. Hévin; Steffan Hansen; Pia Addison; Laure Benoit; Gael J. Kergoat; Julien Haran (Zoologica Scripta, 2022)
The Cape Floristic Region in the Republic of South Africa is a well‐recognized hotspot of biodiversity. Although this region is mostly known for its high level of plant diversity and endemicity, it also hosts an understudied and likely diverse arthropod fauna. Here we investigate the evolutionary history and timing of diversification of the apterous weevil genus Phlyctinus (Curculionidae: Entiminae), which is endemic to the coastal area and adjacent mountain ranges of the Cape floristic region and generally associated with sunflower plants (Asteraceae). We use a diverse array of molecular analyses (phylogenetic inference, molecular species delimitation and dating analyses) to analyse a novel molecular dataset of 202 weevil specimens (including 170 Phlyctinus sampled in 60 sites), and sequenced for two mitochondrial and four nuclear gene fragments. Phylogenetic and dating analyses indicate that the genus started diversifying in the late Miocene, with contrasting diversification dynamics for the three inferred clades, which present disjunct distributions. Host plant records and the lack of relatedness of species living in sympatry indicate that the diversification of Phlyctinus was predominantly driven by allopatric (geographic) speciation. We hypothesize that the interplay between topography and recurring cycles of coastline‐habitat fragmentation resulting from sea level oscillations spurred the diversification of the most speciose clade, whereas in the two remaining clades populations likely remained connected thus hampering allopatric speciation. Interestingly, this pattern echoes with the role of sea level oscillations as an important driver of the radiation of several lineages in the coastline ecosystems of the Cape Floristic Region.

Oceanic giants dance to atmospheric rhythms: Ephemeral wind‐driven resource tracking by blue whales - John P. Ryan; Kelly J. Benoit‐Bird; William K. Oestreich; Paul Leary; Kevin B. Smith; Chad M. Waluk; David E. Cade; James A. Fahlbusch; Brandon L. Southall; John E. Joseph; Tetyana Margolina; John Calambokidis; et al. (Ecology Letters, 2022)
Trophic transfer of energy through marine food webs is strongly influenced by prey aggregation and its exploitation by predators. Rapid aggregation of some marine fish and crustacean forage species during wind‐driven coastal upwelling has recently been discovered, motivating the hypothesis that predators of these forage species track the upwelling circulation in which prey aggregation occurs. We examine this hypothesis in the central California Current Ecosystem using integrative observations of upwelling dynamics, forage species' aggregation, and blue whale movement. Directional origins of blue whale calls repeatedly tracked upwelling plume circulation when wind‐driven upwelling intensified and aggregation of forage species was heightened. Our findings illustrate a resource tracking strategy by which blue whales may maximize energy gain amid ephemeral foraging opportunities. These findings have implications for the ecology and conservation of diverse predators that are sustained by forage populations whose behaviour is responsive to episodic environmental dynamics.

Ten lessons on the resilience of the EU common fisheries policy towards climate change and fuel efficiency - A call for adaptive, flexible and well-informed fisheries management - Francois Bastardie; David A. Feary; Thomas Brunel; Laurence T. Kell; Ralf Döring; Sebastien Metz; Ole R. Eigaard; Oihane C. Basurko; Valerio Bartolino; Jacob Bentley; Benoit Berges; Sieme Bossier; et al. (Frontiers in Marine Science, 2022)
To effectively future-proof the management of the European Union fishing fleets we have explored a suite of case studies encompassing the northeast and tropical Atlantic, the Mediterranean, Baltic and Black Seas. This study shows that European Union (EU) fisheries are likely resilient to climate-driven short-term stresses, but may be negatively impacted by long-term trends in climate change. However, fisheries’ long-term stock resilience can be improved (and therefore be more resilient to increasing changes in climate) by adopting robust and adaptive fisheries management, provided such measures are based on sound scientific advice which includes uncertainty. Such management requires regular updates of biological reference points. Such updates will delineate safe biological limits for exploitation, providing both high long-term yields with reduced risk of stock collapse when affected by short-term stresses, and enhanced compliance with advice to avoid higher than intended fishing mortality. However, high resilience of the exploited ecosystem does not necessarily lead to the resilience of the economy of EU fisheries from suffering shocks associated with reduced yields, neither to a reduced carbon footprint if fuel use increases from lower stock abundances. Fuel consumption is impacted by stock development, but also by changes in vessel and gear technologies, as well as fishing techniques. In this respect, energy-efficient fishing technologies already exist within the EU, though implementing them would require improving the uptake of innovations and demonstrating to stakeholders the potential for both reduced fuel costs and increased catch rates. A transition towards reducing fuel consumption and costs would need to be supported by the setup of EU regulatory instruments. Overall, to effectively manage EU fisheries within a changing climate, flexible, adaptive, well-informed and well-enforced management is needed, with incentives provided for innovations and ocean literacy to cope with the changing conditions, while also reducing the dependency of the capture fishing industry on fossil fuels. To support such management, we provide 10 lessons to characterize ‘win-win’ fishing strategies for the European Union, which develop leverages in which fishing effort deployed corresponds to Maximum Sustainable Yield targets and Common Fisheries Policy minimal effects objectives. In these strategies, higher catch is obtained in the long run, less fuel is spent to attain the catch, and the fisheries have a higher resistance and resilience to shock and long-term factors to face climate-induced stresses.

An Approaching Motor Boat Induces Stress-Related Behaviors in Proboscis Monkeys (Nasalis larvatus) Living in a Riparian Area - Marina Davila-Ross; Helen Pople; Violet Gibson; Senthilvel K. S. S. Nathan; Benoit Goossens; Danica J. Stark (International Journal of Primatology, 2022)
Primate ecotourism is a fast-growing tourism sector that may have a negative effect on wildlife. In riparian areas, tourists can conveniently reach primates via motor boats, but no study has directly examined whether such boats cause stress in primates. Our goal was to test whether the approach of a motor boat induces stress-related and other behaviors in proboscis monkeys ( Nasalis larvatus ), an Endangered species. We studied six one-male, multifemale groups living in a remote riparian area in Sabah, Malaysia, and conducted an experiment by approaching the monkeys in a motor boat by using three conditions with different speeds and travel distances (fast-close, slow-close, and slow-far conditions; 7-8 subjects per condition). For each condition, we compared stress-related behaviors before the boat approach with after the boat started approaching. Feeding, allogrooming and aggression were similarly examined, respectively. We also observed the monkeys’ behaviors at other times to examine age-sex classes differences in vigilance, social proximity, allogrooming, aggression and play (87 subjects). In the experiment, subjects displayed stress-related behaviors for longer in the fast-close and slow-close conditions once the boat started approaching than before the boat approach. The subjects also reduced feeding in the fast-close condition after the boat started approaching. In our observational study, males were more vigilant than females—a behavior that is likely to relate to male-male competition and group protection. This study provides evidence that even a single motor boat moving slowly, with humans behaving calmly, may negatively affect primate behavior and induce stress—an impact that is likely to be larger with tourist boats. Our study also shows that using conditions comparable to the slow-far condition (speed of 3.6 km/hr; no closer than 60 m), where no impact was observed, may help with to develop guidelines for primate tourism in riparian areas. Future research that examines the impact of boats on other primates is needed.

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Suction drainage fluid culture during septic orthopaedic surgery, a retrospective study - C.-A. Hobson; J. Lourtet-Hascoët; A. Mizrahi; N. El Helali; C. Couzigou; A. Mohamed Hadj; R. Courseau; G. Riouallon; F. Boillot; A. Le Monnier; P. Jouffroy; Benoit Pilmis (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

The origin of an extreme case of sister‐species sympatry in a palm‐pollinator mutualistic system - Julien Haran; Laurence Beaudoin‐Ollivier; Laure Benoit; Gael J. Kergoat (Journal of Biogeography, 2021)
Aim Mutualistic systems involving plants and brood pollinators show intriguing cases where a single plant is pollinated by several closely related sympatric species. This study aims at identifying the mechanisms involved in such an extreme case, where 10 sympatric weevil species are only associated with African oil palm inflorescences. We assessed the patterns and timing of speciation of this peculiar assemblage to explore the main drivers of its diversification. Location Tropical Africa. Taxon The African oil palm Elaeis guineensis Jacquin (Arecaceae, Cocoseae), weevil genera Elaeidobius Kuschel and Prosoestus Faust (Curculionidae, Derelomini). Methods We first reassessed the status of the weevil species assemblage associated with the African oil palm based on a range of molecular species delimitation analyses. Second, we reconstructed a dated molecular phylogeny using Bayesian inference and maximum likelihood and carried out historical biogeographical analyses accounting for the main biogeographical barriers in tropical Africa. Results Our analyses generally confirm the validity of the species associated with the African oil palm and indicate that they form a monophyletic group. Dating analyses indicate that they originated about 7–8 million years ago (Mya) and that most speciation events occurred during the Pliocene and Pleistocene. Historical biogeography analyses reveal that one geographical barrier played a bigger role during their diversification. Age estimates suggest that extant weevil species remained in sympatry along the range of their host during the last 0.2 Mya. Main conclusions This case represents a remarkable example of a speciose mutualistic monophyletic insect assemblage. Our results indicate that past climatic oscillations in Western and Central Africa – where cycles of range contractions and expansions of the host drove the divergence of the weevils in allopatry – and the predominant role of a mountain range were instrumental in the emergence of the sympatric assemblage.

Threats of illegal, unregulated, and unreported fishing to biodiversity and food security in the Republic of the Congo - Philip D. Doherty; Benoit C. Atsango; Gaston Ngassiki; Appolinaire Ngouembe; Nathalie Bréheret; Eva Chauvet; Brendan J. Godley; Lucie Machin; Baudelaire Dissondet Moundzoho; Richard J. Parnell; Kristian Metcalfe (Conservation Biology, 2021)
Illegal, unregulated, and unreported (IUU) fishing poses a major threat to effective management of marine resources, affecting biodiversity and communities dependent on these coastal resources. Spatiotemporal patterns of industrial fisheries in developing countries are often poorly understood, and global efforts to describe spatial patterns of fishing vessel activity are currently based on automatic identification system (AIS) data. However, AIS is often not a legal requirement on fishing vessels, likely resulting in underestimates of the scale and distribution of legal and illegal fishing activity, which could have significant ramifications for targeted enforcement efforts and the management of fisheries resources. To help address this knowledge gap, we analyzed 3 years of vessel monitoring system (VMS) data in partnership with the national fisheries department in the Republic of the Congo to describe the behavior of national and distant‐water industrial fleets operating in these waters. We found that the spatial footprint of the industrial fisheries fleet encompassed over one‐quarter of the Exclusive Economic Zone. On average, 73% of fishing activity took place on the continental shelf (waters shallower than 200 m). Our findings highlight that VMS is not acting as a deterrent or being effectively used as a proactive management tool. As much as 33% (13% on average) of fishing effort occurred in prohibited areas set aside to protect biodiversity, including artisanal fisheries resources, and the distant‐water fleet responsible for as much as 84% of this illegal activity. Given the growth in industrial and distant‐water fleets across the region, as well as low levels of management and enforcement, these findings highlight that there is an urgent need for the global community to help strengthen regional and national capacity to analyze national scale data sets if efforts to combat IUU fishing are to be effective.

Chemical Effects of Snowmelt on an Alpine Lake in the Wind River Range, WY - T. R. Ganz; J. McMurray; K. Covey; C. Bettigole; G. Benoit (Water, Air, & Soil Pollution, 2021)

A re-assessment of the oldest therapsid Raranimus confirms its status as a basal member of the clade and fills Olson’s gap - A. Duhamel; J. Benoit; B. S. Rubidge; J. Liu (The Science of Nature, 2021)

Vertical migration timing illuminates the importance of visual and nonvisual predation pressure in the mesopelagic zone - Kelly J. Benoit‐Bird; Mark A. Moline (Limnology and Oceanography, 2021)
Each day, motile pelagic organisms of all sizes undergo vertical movements tied to sunset and sunrise. Diel migration of animals is thought to result from the competing need to feed in energy rich surface waters while avoiding visual predators. Previous study using a newly adapted autonomous vehicle to measure individual characteristics in scattering layers provided the first measures of the internal layer structure, demonstrating that deep scattering layers can be made up of many topologically scaled, mono‐specific aggregations, or “schools.” Follow‐up measurements presented here show these schools of mesopelagic animals remain coherent during upward migration at dusk. We found that groups of smaller animals began migrating sooner each night than larger individuals, consistent with their relatively lower detectability by visual predators. We also found a correlation with taxonomic differences in swimming capabilities, suggesting that the ability to avoid predators if they are encountered also plays a role in the patterns of migration observed. The presence of acoustic predators, Risso's dolphins ( Grampus griseus ), however, altered this pattern for their primary prey, causing squid to remain at depth for approximately 40 min longer than others. The risk of predation by this air‐breathing predator decreases with depth, making delaying migration an appropriate response to this largely nonvisual predation risk. Understanding the timing of individual migration patterns provides insights into the bioenergetic and predator–prey processes in the mesopelagic zone that are critical for understanding the ecological and biogeochemical impacts of these high biomass layers in the ocean.

Cross-tolerance and transcriptional shifts underlying abiotic stress in the seabird tick, Ixodes uriae - Benjamin Davies; Andrew J. Rosendale; Josiah D. Gantz; Richard E. Lee; David L. Denlinger; Joshua B. Benoit (Polar Biology, 2021)

Juvenile corals underpin coral reef carbonate production after disturbance - Jérémy Carlot; Mohsen Kayal; Hunter S. Lenihan; Simon J. Brandl; Jordan M. Casey; Mehdi Adjeroud; Ulisse Cardini; Alexandre Merciere; Benoit Espiau; Diego R. Barneche; Alessio Rovere; Laetitia Hédouin; et al. (Global Change Biology, 2021)
Sea‐level rise is predicted to cause major damage to tropical coastlines. While coral reefs can act as natural barriers for ocean waves, their protection hinges on the ability of scleractinian corals to produce enough calcium carbonate (CaCO 3 ) to keep up with rising sea levels. As a consequence of intensifying disturbances, coral communities are changing rapidly, potentially reducing community‐level CaCO 3 production. By combining colony‐level physiology and long‐term monitoring data, we show that reefs recovering from major disturbances can produce 40% more CaCO 3 than currently estimated due to the disproportionate contribution of juvenile corals. However, the buffering effect of highly productive juvenile corals is compromised by recruitment failures, which have been more frequently observed after large‐scale, repeated bleaching events. While the size structure of corals can bolster a critical ecological function on reefs, climate change impacts on recruitment may undermine this buffering effect, thus further compromising the persistence of reefs and their provision of important ecosystem services.

Legacy and alternative halogenated flame retardants in Lake Geneva fish - Marc Babut; Philippe Marchand; Anaïs Venisseau; Bruno Veyrand; Benoit J. D. Ferrari (Environmental Science and Pollution Research, 2021)

Seeing through the static: the temporal dimension of plant–animal mutualistic interactions - Paul J. CaraDonna; Laura A. Burkle; Benjamin Schwarz; Julian Resasco; Tiffany M. Knight; Gita Benadi; Nico Blüthgen; Carsten F. Dormann; Qiang Fang; Jochen Fründ; Benoit Gauzens; Christopher N. Kaiser‐Bunbury; et al. (Ecology Letters, 2021)
Most studies of plant–animal mutualistic networks have come from a temporally static perspective. This approach has revealed general patterns in network structure, but limits our ability to understand the ecological and evolutionary processes that shape these networks and to predict the consequences of natural and human‐driven disturbance on species interactions. We review the growing literature on temporal dynamics of plant–animal mutualistic networks including pollination, seed dispersal and ant defence mutualisms. We then discuss potential mechanisms underlying such variation in interactions, ranging from behavioural and physiological processes at the finest temporal scales to ecological and evolutionary processes at the broadest. We find that at the finest temporal scales (days, weeks, months) mutualistic interactions are highly dynamic, with considerable variation in network structure. At intermediate scales (years, decades), networks still exhibit high levels of temporal variation, but such variation appears to influence network properties only weakly. At the broadest temporal scales (many decades, centuries and beyond), continued shifts in interactions appear to reshape network structure, leading to dramatic community changes, including loss of species and function. Our review highlights the importance of considering the temporal dimension for understanding the ecology and evolution of complex webs of mutualistic interactions.

Ecotoxicological testing of sediments and dredged material: an overlooked opportunity? - Susanne Heise; Marc Babut; Carmen Casado; Ute Feiler; Benoit J. D. Ferrari; Laura Marziali (Journal of Soils and Sediments, 2020)
Purpose Basing decisions for the management of contaminated sediments on ecotoxicological data is still often met with skepticism by European stakeholders. These concerns are discussed as they pertain to bioassays to show how ecotoxicological data may provide added value for the sustainable management of sediment in aquatic systems. Materials and methods Five “concerns” are selected that are often raised by stakeholders. The ecotoxicological practice is discussed in light of the knowledge gained in recent decades and compared with chemical sediment analysis and chemical data. Results and discussion Common assumptions such as a higher uncertainty of biotest results for sediments compared to chemical analyses are not supported by interlaboratory comparisons. Some confusion also arises, because the meaning of biotest data is often misunderstood, questioning their significance in light of a limited number of organisms and altered test conditions in the lab. Because biotest results describe a sediment property, they should not be directly equated with an impact upon the biological community. To identify a hazard, however, the possibility of false-negative results due to the presence of contaminants that are not analyzed but are toxic is lower. Conclusions The cost of increased investment in ecotoxicological tests is, in our view, small compared with that of making false-negative assessments of sediment/dredged material that can ultimately have long-term environmental costs. As such, we conclude that ecotoxicological testing is an opportunity for sediment management decision-making that warrants more attention and confidence in Europe.

Microhaplotype genotyping-by-sequencing of 98 highly polymorphic markers in three chestnut tree species - Benoit Laurent; Clément Larue; Emilie Chancerel; Erwan Guichoux; Rémy J. Petit; Teresa Barreneche; Cécile Robin; Olivier Lepais (Conservation Genetics Resources, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Biology and biotechnological applications of microalgae and photosynthetic prokaryotes: part 2 - Julian J. Eaton-Rye; Benoit Guieysse; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2020)

Changes in Deadwood and Understory Vegetation 12 Years after Partial and Clearcut Harvesting in Mixedwood Stands of Western Quebec, Canada - Kobra Maleki; Benoit Lafleur; Brian D Harvey; Marc J Mazerolle; Nicole J Fenton (Forest Science, 2020)
Ecosystem management promotes the integration of knowledge of natural ecosystem dynamics into forest-management planning and practices, and provides a useful framework for understanding and mitigating the impacts of timber harvesting on biodiversity and ecosystem functions. Understory vegetation and deadwood are involved in many ecosystem functions including nutrient and carbon, and tree-regeneration dynamics. The study objective was to compare the 12-year post-treatment effects on forest floor attributes of two intensities of partial harvesting (gap harvesting [62 percent basal area retention; BAR] and diameter-limit harvesting [35 percent BAR]) to clearcutting (10 percent BAR). We quantified the standing and downed deadwood abundance and the understory plant community composition in mixed, northern temperate forests, in western Québec, Canada. Our results suggest that moderate-intensity gap harvesting can best preserve a standing deadwood stem density and a diameter structure comparable to unmanaged stands. Downed deadwood abundance of all diameter classes was not altered, 12 years following the gap harvesting. Finally, understory plant communities in the gap treatment were more similar to those of unmanaged stands than those in diameter-limit and clearcutting treatments. These results illustrate the importance of tree retention levels for the maintenance of deadwood and understory plant species associated with closed-canopy or old-growth forests.

Stress or injury induces cellular plasticity in salivary gland acinar cells - Andrew D. Shubin; Azmeer Sharipol; Timothy J. Felong; Pei-Lun Weng; Brittany E. Schutrum; Debria S. Joe; Marit H. Aure; Danielle S.W. Benoit; Catherine E. Ovitt (Cell and Tissue Research, 2020)

Differences in attentional control and white matter microstructure in adolescents with attentional, affective, and behavioral disorders - Andrea T. Shafer; James R. Benoit; Matthew R. G. Brown; Andy J. Greenshaw; K. Jessica Van Vliet; Sunita Vohra; Florin Dolcos; Anthony Singhal (Brain Imaging and Behavior, 2020)

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The Antarctic mite, Alaskozetes antarcticus, shares bacterial microbiome community membership but not abundance between adults and tritonymphs - Christopher J. Holmes; Emily C. Jennings; J. D. Gantz; Drew Spacht; Austin A. Spangler; David L. Denlinger; Richard E. Lee; Trinity L. Hamilton; Joshua B. Benoit (Polar Biology, 2019)

Precipitation mediates sap flux sensitivity to evaporative demand in the neotropics - Charlotte Grossiord; Bradley Christoffersen; Aura M. Alonso-Rodríguez; Kristina Anderson-Teixeira; Heidi Asbjornsen; Luiza Maria T. Aparecido; Z. Carter Berry; Christopher Baraloto; Damien Bonal; Isaac Borrego; Benoit Burban; Jeffrey Q. Chambers; et al. (Oecologia, 2019)

The neutrophil to lymphocyte ratio indexes individual variation in the behavioural stress response of wild roe deer across fluctuating environmental conditions - Jeffrey Carbillet; Benjamin Rey; Typhaine Lavabre; Yannick Chaval; Joël Merlet; François Débias; Corinne Régis; Sylvia Pardonnet; Jeanne Duhayer; Jean-Michel Gaillard; A. J. M. Hewison; Jean-François Lemaître; et al. (Behavioral Ecology and Sociobiology, 2019)

LRP1 Has a Predominant Role in Production over Clearance of Aβ in a Mouse Model of Alzheimer’s Disease - Bart Van Gool; Steffen E. Storck; Sara M. Reekmans; Benoit Lechat; Philip L. S. M. Gordts; Laurent Pradier; Claus U. Pietrzik; Anton J. M. Roebroek (Molecular Neurobiology, 2019)

Seed dispersal by proboscis monkeys: the case of Nauclea spp. - Valentine Thiry; Oriana Bhasin; Danica J. Stark; Roseline C. Beudels-Jamar; Régine Vercauteren Drubbel; Senthilvel K. S. S. Nathan; Benoit Goossens; Martine Vercauteren (Primates, 2019)

Combined Feedforward/Feedback Control of an Integrated Continuous Granulation Process - Glinka Cathy Pereira; Shashank Venkat Muddu; Andrés David Román-Ospino; Don Clancy; Benoit Igne; Christian Airiau; Fernando J. Muzzio; Marianthi Ierapetritou; Rohit Ramachandran; Ravendra Singh (Journal of Pharmaceutical Innovation, 2019)

Voluntary Restoration: Mitigation's Silent Partner in the Quest to Reverse Coastal Wetland Loss in the USA - Rachel K. Gittman; Christopher J. Baillie; Katie K. Arkema; Richard O. Bennett; Jeff Benoit; Seth Blitch; Julien Brun; Anthony Chatwin; Allison Colden; Alyssa Dausman; Bryan DeAngelis; Nathaniel Herold; et al. (Frontiers in Marine Science, 2019)

Observing System Evaluation Based on Ocean Data Assimilation and Prediction Systems: On-Going Challenges and a Future Vision for Designing and Supporting Ocean Observational Networks - Yosuke Fujii; Elisabeth Rémy; Hao Zuo; Peter Oke; George Halliwell; Florent Gasparin; Mounir Benkiran; Nora Loose; James Cummings; Jiping Xie; Yan Xue; Shuhei Masuda; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Extended-pulsed fidaxomicin versus vancomycin for Clostridium difficile infection: EXTEND study subgroup analyses - Oliver A. Cornely; Maria J. G. T. Vehreschild; Nicholas Adomakoh; Areti Georgopali; Andreas Karas; Gbenga Kazeem; Benoit Guery (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Biology and biotechnological applications of microalgae and photosynthetic prokaryotes: Part 1 - Julian J. Eaton‐Rye; Benoit Guieysse; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2019)

Sex- and developmental-specific transcriptomic analyses of the Antarctic mite, Alaskozetes antarcticus, reveal transcriptional shifts underlying oribatid mite reproduction - Hannah E. Meibers; Geoffrey Finch; Robert T. Gregg; Sierra Glenn; Keavash D. Assani; Emily C. Jennings; Benjamin Davies; Andrew J. Rosendale; Christopher J. Holmes; J. D. Gantz; Drew E. Spacht; Richard E. Lee; et al. (Polar Biology, 2019)

Progressive behavioural, physiological and transcriptomic shifts over the course of prolonged starvation in ticks - Andrew J. Rosendale; Megan E. Dunlevy; Marshall D. McCue; Joshua B. Benoit (Molecular Ecology, 2019)
Ticks are obligatorily hematophagous but spend the majority of their lives off host in an unfed state where they must resist starvation between bouts of blood feeding. Survival during these extended off‐host periods is critical to the success of these arthropods as vectors of disease; however, little is known about the underlying physiological and molecular mechanisms of starvation tolerance in ticks. We examined the bioenergetic, transcriptomic and behavioural changes of female American dog ticks, Dermacentor variabilis , throughout starvation (up to nine months post‐bloodmeal). As starvation progressed, ticks utilized glycogen and lipid, and later protein as energy reserves with proteolysis and autophagy facilitating the mobilization of endogenous nutrients. The metabolic rate of the ticks was expectedly low, but showed a slight increase as starvation progressed possibly reflecting the upregulation of several energetically costly processes such as transcription/translation and/or increases in host‐seeking behaviours. Starved ticks had higher activity levels, increased questing behaviour and augmented expression of genes related to chemosensing, immunity and salivary gland proteins. The shifts in gene expression and associated behavioural and physiological processes are critical to allowing these parasites to exploit their ecological niche as extreme sit‐and‐wait parasites. The overall responses of ticks to starvation were similar to other blood‐feeding arthropods, but we identified unique responses that could have epidemiological and ecological significance for ticks as ectoparasites that must be tolerant of sporadic feeding.

A novel method to infer historical DDT use on Cape Cod, Massachusetts (USA), based on ΣDDT degradation and 210Pb dating in lake sediment cores - Beth J. Feingold; Gaboury Benoit (Journal of Paleolimnology, 2018)

Development and implementation of eco-genomic tools for aquatic ecosystem biomonitoring: the SYNAQUA French-Swiss program - Estelle Lefrançois; Laure Apothéloz-Perret-Gentil; Philippe Blancher; Samuel Botreau; Cécile Chardon; Laura Crepin; Tristan Cordier; Arielle Cordonier; Isabelle Domaizon; Benoit J. D. Ferrari; Julie Guéguen; Jean-Christophe Hustache; et al. (Environmental Science and Pollution Research, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Erratum to: Western US high June 2015 temperatures and their relation to global warming and soil moisture - Sjoukje Y. Philip; Sarah F. Kew; Mathias Hauser; Benoit P. Guillod; Adriaan J. Teuling; Kirien Whan; Peter Uhe; Geert Jan van Oldenborgh (Climate Dynamics, 2018)

Western US high June 2015 temperatures and their relation to global warming and soil moisture - Sjoukje Y. Philip; Sarah F. Kew; Mathias Hauser; Benoit P. Guillod; Adriaan J. Teuling; Kirien Whan; Peter Uhe; Geert Jan van Oldenborgh (Climate Dynamics, 2018)

Rapid Screening of Potato Cultivars Tolerant to Nitrogen Deficiency Using a Hydroponic System - Xiaofang Xie; Xiu-Qing Li; Bernie J. Zebarth; Suyan Niu; Ruimin Tang; Helen H. Tai; Benoit Bizimungu; Weiren Wu; Muhammad Haroon (American Journal of Potato Research, 2018)

Prey in oceanic sound scattering layers organize to get a little help from their friends - Kelly J. Benoit‐Bird; Mark A. Moline; Brandon L. Southall (Limnology and Oceanography, 2017)
Group formation in animals is a widespread phenomenon driven by food acquisition, reproduction, and defense. Life in the ocean is characteristically aggregated into horizontally extensive layers as a result of strong vertical gradients in the environment. Each day, animals in high biomass aggregations called “deep scattering layers” migrate vertically, comprising the largest net animal movement on earth. This movement is commonly thought of as a predator avoidance tactic, however, the aggregation of animals into layers has been viewed as an incidental outcome of similar responses by many individuals to the risk of visual predation coupled with the location of resources including food and oxygen rather than active, socially mediated congregation for defense purposes. Here, using a newly adapted autonomous vehicle to measure individual characteristics, we provide the first measures of the internal layer structure, demonstrating that these features are made up of many topologically scaled, mono‐specific aggregations, or “schools” rather than an indiscriminate mix of sizes and species. Schools responded to predators using behavior much like flash compression while neighboring aggregations increased their spacing to maintain coherent layers. Rather than simply an incidental outcome, the formation of layers of life in the sea is a highly organized process driven, at least in part, by biotic pressures for cohesion with broad adaptive significance for the myriad species that inhabit these ubiquitous features. These observations highlight the range of spatial scales we must examine in order to understand the strong impacts these high‐biomass layers have on ecological and biogeochemical processes in the sea.

Mind the cell: Seasonal variation in telomere length mirrors changes in leucocyte profile - Michaël Beaulieu; Laure Benoit; Steven Abaga; Peter M. Kappeler; Marie J. E. Charpentier (Molecular Ecology, 2017)
Leucocytes are typically considered as a whole in studies examining telomere dynamics in mammals. Such an approach may be precarious, as leucocytes represent the only nucleated blood cells in mammals, their composition varies temporally, and telomere length differs between leucocyte types. To highlight this limitation, we examined here whether seasonal variation in leucocyte composition was related to variation in telomere length in free‐ranging mandrills ( Mandrilllus sphinx ). We found that the leucocyte profile of mandrills varied seasonally, with lower lymphocyte proportion being observed during the long dry season presumably because of the combined effects of high nematode infection and stress at that time of the year. Interestingly, this low lymphocyte proportion during the long dry season was associated with shorter telomeres. Accordingly, based on longitudinal data, we found that seasonal changes in lymphocyte proportion were reflected by corresponding seasonal variation in telomere length. Overall, these results suggest that variation in lymphocyte proportion in blood can significantly affect telomere measurements in mammals. However, lymphocyte proportion did not entirely explain variation in telomere length. For instance, a lower lymphocyte proportion with age could not fully explain shorter telomeres in older individuals. Overall, our results show that telomere length and leucocyte profile are strongly although imperfectly intertwined, which may obscure the relationship between telomere dynamics and ageing processes in mammals.

Comparative analysis of spatial genetic structure in an ant–plant symbiosis reveals a tension zone and highlights speciation processes in tropical Africa - Rumsaïs Blatrix; Jean Peccoud; Céline Born; Finn Piatscheck; Laure Benoit; Mathieu Sauve; Champlain Djiéto‐Lordon; Christiane Atteke; Jan J. Wieringa; David J. Harris; Doyle McKey (Journal of Biogeography, 2017)
Aim Pleistocene climatic oscillations induced range fluctuations in African rain forest organisms and may have shaped species diversification through allopatric speciation events. We compared the spatial genetic structure of two forest species that live in obligate symbiosis and thus must have experienced the same range fluctuations, as a means to discriminate incipient speciation from transient differentiation simply resulting from past divergence. Location Western central Africa. Methods We genotyped 765 individuals of the tree Barteria fistulosa and 605 colonies of its symbiotic ant Tetraponera aethiops at 12 and 13 microsatellite loci, respectively. We compared the spatial genetic structure of the two symbionts by using Bayesian clustering algorithms, isolation‐by‐distance analyses and clines of synthetic alleles. We used species niche modelling (climatic and soil variables) to investigate ecological variables associated with genetic discontinuities in tree populations. Results The trees and the ants showed congruent patterns of spatial genetic structure. However, the trees showed a very steep genetic discontinuity between groups north and south of latitude 1° N, which was much weaker in the ants. There was no evidence for effective gene flow between the two tree lineages in contact at the transition zone, despite the presence of a few hybrids. Niche modelling did not predict the occurrence of northern trees south of this genetic transition, and vice versa. Main conclusions The genetic discontinuity near latitude 1° N is inferred to be a tension zone resulting from reproductive incompatibilities between previously allopatric tree lineages. This tension zone may have stabilized at a climatic transition (between boreal and austral seasonal regimes), and matches patterns of genetic structure previously observed in other forest plant species. Our results illustrate independent speciation between two species that live in specific and obligate symbiosis and suggest that a tension zone may separate lineages of several central African forest plants near the thermal equator.

Pedigree Reconstruction with Genome-Wide Markers in Potato - Jeffrey B. Endelman; Cari A. Schmitz Carley; David S. Douches; Joseph J. Coombs; Benoit Bizimungu; Walter S. De Jong; Kathleen G. Haynes; David G. Holm; J. Creighton Miller; Richard G. Novy; Jiwan P. Palta; David L. Parish; et al. (American Journal of Potato Research, 2017)

How does a restored oyster reef develop? An assessment based on stable isotopes and community metrics - Ryan J. Rezek; Benoit Lebreton; E. Brendan Roark; Terence A. Palmer; Jennifer Beseres Pollack (Marine Biology, 2017)

Introduction: proceedings of the 2015 New Zealand symposium on algae and photosynthetic prokaryotes - Michael A. Packer; Julian J. Eaton‐Rye; Tina C. Summerfield; Benoit Guieysse; Susanna A. Wood (New Zealand Journal of Botany, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Habitat availability and geographic isolation as potential drivers of population structure in an oceanic dolphin in the Southwest Indian Ocean - Amélia Viricel; Benoit Simon-Bouhet; Laura Ceyrac; Violaine Dulau-Drouot; Per Berggren; Omar A. Amir; Narriman S. Jiddawi; Philippe Mongin; Jeremy J. Kiszka (Marine Biology, 2016)

Toluene diisocyanate and methylene diphenyl diisocyanate: asthmatic response and cross-reactivity in a mouse model - Lore Pollaris; Fien Devos; Vanessa De Vooght; Sven Seys; Benoit Nemery; Peter H. M. Hoet; Jeroen A. J. Vanoirbeek (Archives of Toxicology, 2016)

Simulations of the flow in the Mahakam river–lake–delta system, Indonesia - Chien Pham Van; Benjamin de Brye; Eric Deleersnijder; A. J. F. Hoitink; Maximiliano Sassi; Benoit Spinewine; Hidayat Hidayat; Sandra Soares-Frazão (Environmental Fluid Mechanics, 2016)

Improving cellulase production by Aspergillus niger using adaptive evolution - Aleksandrina Patyshakuliyeva; Mark Arentshorst; Iris E. Allijn; Arthur F. J. Ram; Ronald P. de Vries; Isabelle Benoit Gelber (Biotechnology Letters, 2016)

Short day-triggered quiescence promotes water conservation in the American dog tick, Dermacentor variabilis - Jay A. Yoder; Andrew J. Rosendale; Joshua B. Benoit (Journal of Comparative Physiology B, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Physiological implications of the abnormal absence of the parietal foramen in a late Permian cynodont (Therapsida) - Julien Benoit; Fernando Abdala; Marc J. Van den Brandt; Paul R. Manger; Bruce S. Rubidge (The Science of Nature, 2015)

Using multi‐timescale methods and satellite‐derived land surface temperature for the interpolation of daily maximum air temperature in Oregon - Benoit Parmentier; Brian J. McGill; Adam M. Wilson; James Regetz; Walter Jetz; Robert Guralnick; Mao‐Ning Tuanmu; Mark Schildhauer (International Journal of Climatology, 2015)
There is a growing demand for fine‐grained (e.g. 1 km) daily historical meteorological data. Traditional approaches interpolate between observations collected at existing meteorological stations; however, the demand for ever increasing fine resolutions has begun to outstrip the available ground‐station data, especially for daily timescales. One promising technique known as the climate‐aided interpolation ( CAI ) has the advantage of incorporating climatological data to improve fine‐grained spatial detail while still producing a daily product. By estimating spatial structure at a coarser timescale than the target timescale, more ground‐station data can be used, leading to improved accuracy in these multi‐timescale procedures. Another approach to improve fine‐grained spatial structure is the incorporation of additional environmental covariates that are measured at fine grains. Elevation has long been used in this role, but other covariates, especially remotely sensed measures of land cover and land surface temperatures ( LST ), are also promising. In this paper, we provide a comprehensive evaluation of three interpolation methods and rigorous evaluation of multi‐timescale procedures that do and do not include additional environmental covariates including LST . We perform this evaluation on daily maximum air temperature predictions using a region with widely varying climates, the state of Oregon, USA . We find that multi‐timescale procedures provide a roughly 10% improvement in prediction accuracy over single‐timescale procedures. For multi‐timescale approaches, we find that universal kriging has the lowest root mean square error ( RMSE ) but has a lower predictive accuracy when the number of station decreases in the study area. Thus, generalized additive models ( GAM ) and geographically weighted regression ( GWR ) may be superior interpolation methods in areas with sparse station data. Most covariates other than elevation do not improve accuracy, but LST may be useful during summer when elevation displays low correlation with T max . Analyses also show that elevation and LST provide increased spatial heterogeneity.

Neurofilament dynamics and involvement in neurological disorders - Benoit J. Gentil; Michael Tibshirani; Heather D. Durham (Cell and Tissue Research, 2015)

B acillus subtilis attachment to A spergillus niger hyphae results in mutually altered metabolism - Isabelle Benoit; Marielle H. van den Esker; Aleksandrina Patyshakuliyeva; Derek J. Mattern; Felix Blei; Miaomiao Zhou; Jan Dijksterhuis; Axel A. Brakhage; Oscar P. Kuipers; Ronald P. de Vries; Ákos T. Kovács (Environmental Microbiology, 2015)
Summary Interaction between microbes affects the growth, metabolism and differentiation of members of the microbial community. While direct and indirect competition, like antagonism and nutrient consumption have a negative effect on the interacting members of the population, microbes have also evolved in nature not only to fight, but in some cases to adapt to or support each other, while increasing the fitness of the community. The presence of bacteria and fungi in soil results in various interactions including mutualism. Bacilli attach to the plant root and form complex communities in the rhizosphere. B acillus subtilis , when grown in the presence of A spergillus niger , interacts similarly with the fungus, by attaching and growing on the hyphae. Based on data obtained in a dual transcriptome experiment, we suggest that both fungi and bacteria alter their metabolism during this interaction. Interestingly, the transcription of genes related to the antifungal and putative antibacterial defence mechanism of B . subtilis and A . niger , respectively, are decreased upon attachment of bacteria to the mycelia. Analysis of the culture supernatant suggests that surfactin production by B . subtilis was reduced when the bacterium was co‐cultivated with the fungus. Our experiments provide new insights into the interaction between a bacterium and a fungus.

Reconstructing the demographic history of orang‐utans using Approximate B ayesian Computation - Alexander Nater; Maja P. Greminger; Natasha Arora; Carel P. van Schaik; Benoit Goossens; Ian Singleton; Ernst J. Verschoor; Kristin S. Warren; Michael Krützen (Molecular Ecology, 2015)
Investigating how different evolutionary forces have shaped patterns of DNA variation within and among species requires detailed knowledge of their demographic history. O rang‐utans, whose distribution is currently restricted to the S outh‐ E ast A sian islands of B orneo ( P ongo pygmaeus ) and S umatra ( P ongo abelii ), have likely experienced a complex demographic history, influenced by recurrent changes in climate and sea levels, volcanic activities and anthropogenic pressures. Using the most extensive sample set of wild orang‐utans to date, we employed an Approximate B ayesian Computation ( ABC ) approach to test the fit of 12 different demographic scenarios to the observed patterns of variation in autosomal, X ‐chromosomal, mitochondrial and Y ‐chromosomal markers. In the best‐fitting model, Sumatran orang‐utans exhibit a deep split of populations north and south of L ake T oba, probably caused by multiple eruptions of the T oba volcano. In addition, we found signals for a strong decline in all S umatran populations ~24 ka, probably associated with hunting by human colonizers. In contrast, B ornean orang‐utans experienced a severe bottleneck ~135 ka, followed by a population expansion and substructuring starting ~82 ka, which we link to an expansion from a glacial refugium. We showed that orang‐utans went through drastic changes in population size and connectedness, caused by recurrent contraction and expansion of rainforest habitat during Pleistocene glaciations and probably hunting by early humans. Our findings emphasize the fact that important aspects of the evolutionary past of species with complex demographic histories might remain obscured when applying overly simplified models.

Using next-generation sequencing methods to isolate and characterize 24 simple sequence repeat loci in mandrills (Mandrillus sphinx) - Laure Benoit; Sylvère Mboumba; E. Willaume; P. M. Kappeler; Marie J. E. Charpentier (Conservation Genetics Resources, 2014)

OsJAR1 is required for JA-regulated floret opening and anther dehiscence in rice - Yuguo Xiao; Yi Chen; Tatsiana Charnikhova; Patrick P. J. Mulder; Jeroen Heijmans; Angela Hoogenboom; Adamantia Agalou; Corinne Michel; Jean-Benoit Morel; Ludovico Dreni; Martin M. Kater; Harro Bouwmeester; et al. (Plant Molecular Biology, 2014)

Stratification and mixing regimes in biological thin layers over the Mid‐Atlantic Bight - E. L. Shroyer; K. J. Benoit-Bird,; J. D. Nash; J. N. Moum (Limnology and Oceanography, 2014)
We use density and microstructure data to characterize the properties and physical setting of optical thin layers observed over the New Jersey shelf in the summer of 2006. Layers were differentiated into two types by their vertical position in the water column, fluorescence intensity, and possibly community composition or cell condition as indicated by the measured differences in the ratio of fluorescence to optical backscatter. Both layer types were associated with gradients in stratification; but, the turbulent mixing environment for the two layer types differed significantly. Shallow layers were located within the pycnocline near the maximum stratification and were exposed to strong turbulence within the surface mixed layer. Consequently, turbulent mixing of buoyancy may have been a key factor in maintaining shallow layers. In contrast, relatively weak density gradients and mixing indicate that turbulent processes may have been less critical for deep layers, which were located at the base of the pycnocline. More generally, both shallow and deep layers were geographically located in regions of low median and high mean turbulent kinetic energy dissipation, i.e., regions of rare yet intense mixing events. This work highlights the need to understand the detailed statistics of mixing at time and vertical scales relevant to thin layers, and more specifically, the need to discern the time history of mixing of the fluid that composes layers.

Land transitions from multivariate time series: using seasonal trend analysis and segmentation to detect land-cover changes - Benoit Parmentier; J. Ronald Eastman (International Journal of Remote Sensing, 2014)

Extreme plasticity in life‐history strategy allows a migratory predator (jumbo squid) to cope with a changing climate - Henk‐Jan T. Hoving; William F. Gilly; Unai Markaida; Kelly J. Benoit‐Bird; Zachary W. ‐Brown; Patrick Daniel; John C. Field; Liz Parassenti; Bilin Liu; Bernardita Campos (Global Change Biology, 2013)
Dosidicus gigas (jumbo or Humboldt squid) is a semelparous, major predator of the eastern Pacific that is ecologically and commercially important. In the Gulf of California, these animals mature at large size (>55 cm mantle length) in 1–1.5 years and have supported a major commercial fishery in the Guaymas Basin during the last 20 years. An El Niño event in 2009–2010, was accompanied by a collapse of this fishery, and squid in the region showed major changes in the distribution and life‐history strategy. Large squid abandoned seasonal coastal‐shelf habitats in 2010 and instead were found in the Salsipuedes Basin to the north, an area buffered from the effects of El Niño by tidal upwelling and a well‐mixed water column. The commercial fishery also relocated to this region. Although large squid were not found in the Guaymas Basin from 2010 to 2012, small squid were abundant and matured at an unusually small mantle‐length ( D. gigas to rapidly adapt to and cope with El Niño. This ability is likely to be an important factor in conjunction with longerterm climate‐change and the potential ecological impacts of this invasive predator on marine ecosystems.

Archaeal diversity from hydrothermal systems of Deception Island, Antarctica - Maximiliano J. Amenábar; Patricio A. Flores; Benoit Pugin; Freddy A. Boehmwald; Jenny M. Blamey (Polar Biology, 2013)

Coumatetralyl resistance of Rattus tanezumi infesting oil palm plantations in Indonesia - J. Andru; J. F. Cosson; J. P. Caliman; E. Benoit (Ecotoxicology, 2013)

Where do adaptive shifts occur during invasion? A multidisciplinary approach to unravelling cold adaptation in a tropical ant species invading the Mediterranean area - Olivier Rey; Arnaud Estoup; Merav Vonshak; Anne Loiseau; Simon Blanchet; Luis Calcaterra; Lucila Chifflet; Jean‐Pierre Rossi; Gaël J. Kergoat; Julien Foucaud; Jérôme Orivel; Maurice Leponce; et al. (Ecology Letters, 2012)
Evolution may improve the invasiveness of populations, but it often remains unclear whether key adaptation events occur after introduction into the recipient habitat (i.e. post‐introduction adaptation scenario), or before introduction within the native range (i.e. prior‐adaptation scenario) or at a primary site of invasion (i.e. bridgehead scenario). We used a multidisciplinary approach to determine which of these three scenarios underlies the invasion of the tropical ant Wasmannia auropunctata in a Mediterranean region (i.e. Israel). Species distribution models ( SDM ), phylogeographical analyses at a broad geographical scale and laboratory experiments on appropriate native and invasive populations indicated that Israeli populations followed an invasion scenario in which adaptation to cold occurred at the southern limit of the native range before dispersal to Israel. We discuss the usefulness of combining SDM , genetic and experimental approaches for unambiguous determination of eco‐evolutionary invasion scenarios.

Genotype by environment interaction effects on fibre components in potato (Solanum tuberosum L.) - Stephanie Bach; Rickey Y. Yada; Benoit Bizimungu; J. Alan Sullivan (Euphytica, 2012)
Increasing awareness of heart health and disease prevention has led consumers to more proactive grocery food choices. Fibre and its associated health benefits remains an important area of research given the current interest in food, nutrition, and health. To position the potato as a good source of fibre, breeding efforts have focused on developing cultivars and germplasm with high fibre content. The current study examined eight elite potato clones and four commercial cultivars (checks) across six environments (three locations over two years) for their total dietary fibre (TDF), neutral detergent fibre (NDF), and soluble fibre (SF) content. Genotype by environment interaction (GEI) and stability analysis were conducted with SAS and GGE Biplot software. Significant genotypic (G), environmental (E) and GEI effects were found. The six environments differed in temperature and moisture levels, which were linked to levels of NDF and TDF. Some genotypes had high levels of stability for fibre content. GGE biplot analysis found no significant mega-environments for fibre components. Two elite clones (CV96044-3 and F05081) were identified as high fibre sources (13.3 and 14.4 %, respectively) compared to the other elite clones and commercial cultivars (e.g., Russet Burbank: 11.7 %). These lines may also be suitable as parents with high fibre and stability to breed into backgrounds with other desirable qualities.

Breast and ovarian cancer risk management in a French cohort of 158 women carrying a BRCA1 or BRCA2 germline mutation: patient choices and outcome - Pascale This; Anne de la Rochefordière; Alexia Savignoni; Marie Christine Falcou; Anne Tardivon; Fabienne Thibault; Séverine Alran; Virgine Fourchotte; Alfred Fitoussi; Benoit Couturaud; Sylvie Dolbeault; Remy J. Salmon; et al. (Familial Cancer, 2012)

Observations of Thin Layers in Coastal Hawaiian Waters - Margaret A. McManus; Jeff C. Sevadjian; Kelly J. Benoit-Bird; Olivia M. Cheriton; Amanda H. V. Timmerman; Chad M. Waluk (Estuaries and Coasts, 2012)

Refining instrument attachment on phocid seals - Iain C. Field; Robert G. Harcourt; Lars Boehme; P. J. Nico de Bruyn; Jean‐Benoit Charrassin; Clive R. McMahon; Marthán N. Bester; Mike A. Fedak; Mark A. Hindell (Marine Mammal Science, 2012)

Disruption of ant-seed dispersal mutualisms by the invasive Asian needle ant (Pachycondyla chinensis) - Mariano A. Rodriguez-Cabal; Katharine L. Stuble; Benoit Guénard; Robert R. Dunn; Nathan J. Sanders (Biological Invasions, 2012)

Multiple traumatic insemination events reduce the ability of bed bug females to maintain water balance - Joshua B. Benoit; Andrew J. Jajack; Jay A. Yoder (Journal of Comparative Physiology B, 2012)

Genetic structure in a dynamic baboon hybrid zone corroborates behavioural observations in a hybrid population - M. J. E. CHARPENTIER; M. C. FONTAINE; E. CHEREL; J. P. RENOULT; T. JENKINS; L. BENOIT; N. BARTHÈS; S. C. ALBERTS; J. TUNG (Molecular Ecology, 2012)
Behaviour and genetic structure are intimately related: mating patterns and patterns of movement between groups or populations influence the movement of genetic variation across the landscape and from one generation to the next. In hybrid zones, the behaviour of the hybridizing taxa can also impact the incidence and outcome of hybridization events. Hybridization between yellow baboons and anubis baboons has been well documented in the Amboseli basin of Kenya, where more anubis‐like individuals tend to experience maturational and reproductive advantages. However, it is unknown whether these advantages are reflected in the genetic structure of populations surrounding this area. Here, we used microsatellite genotype data to evaluate the structure and composition of baboon populations in southern Kenya. Our results indicate that, unlike for mitochondrial DNA, microsatellite‐based measures of genetic structure concord with phenotypically based taxonomic distinctions and that the currently active hybrid zone is relatively narrow. Isolation with migration analysis revealed asymmetric gene flow in this region from anubis populations into yellow populations, in support of the anubis‐biased phenotypic advantages observed in Amboseli. Populations that are primarily yellow but that receive anubis gene flow exhibit higher levels of genetic diversity than yellow populations far from the introgression front. Our results support previous work that indicates a long history of hybridization and introgression among East African baboons. Specifically, it suggests that anubis baboons are in the process of gradual range expansion into the range of yellow baboons, a pattern potentially explained by behavioural and life history advantages that correlate with anubis ancestry.

Growth and nutrition of black spruce seedlings in response to disruption of Pleurozium and Sphagnum moss carpets in boreal forested peatlands - Benoit Lafleur; David Paré; Nicole J. Fenton; Yves Bergeron (Plant and Soil, 2011)

Are water vole resistant to anticoagulant rodenticides following field treatments? - Julie Vein; Agnès Grandemange; Jean-François Cosson; Etienne Benoit; Philippe J. Berny (Ecotoxicology, 2011)

Increased cave dwelling reduces the ability of cave crickets to resist dehydration - Jay A. Yoder; Joshua B. Benoit; Michael J. LaCagnin; Horton H. Hobbs (Journal of Comparative Physiology B, 2011)

Pelagic food web patterns: do they modulate virus and nanoflagellate effects on picoplankton during the phytoplankton spring bloom? - Pascaline Ory; Hans J. Hartmann; Florence Jude; Christine Dupuy; Yolanda Del Amo; Philippe Catala; Françoise Mornet; Valérie Huet; Benoit Jan; Dorothée Vincent; Benoit Sautour; Hélène Montanié (Environmental Microbiology, 2010)
Summary As agents of mortality, viruses and nanoflagellates impact on picoplankton populations. We examined the differences in interactions between these compartments in two French Atlantic bays. Microbes, considered here as central actors of the planktonic food web, were first monitored seasonally in Arcachon (2005) and Marennes‐Oléron (2006) bays. Their dynamics were evaluated to categorize trophic periods using the models of Legendre and Rassoulzadegan as a reference framework. Microbial interactions were then compared through 48 h batch culture experiments performed during the phytoplankton spring bloom, identified as herbivorous in Marennes and multivorous in Arcachon. Marennes was spatially homogeneous compared with Arcachon. The former was potentially more productive, featuring a large number of heterotrophic pathways, while autotrophic mechanisms dominated in Arcachon. A link was found between viruses and phytoplankton in Marennes, suggesting a role of virus in the regulation of autotroph biomass. Moreover, the virus–bacteria relation was weaker in Marennes, with a bacterial lysis potential of 2.6% compared with 39% in Arcachon. The batch experiments (based on size‐fractionation and viral enrichment) revealed different microbial interactions that corresponded to the spring‐bloom trophic interactions in each bay. In Arcachon, where there is a multivorous web, flagellate predation and viral lysis acted in an opposite way on picophytoplankton. When together they both reduced viral production. Conversely, in Marennes (herbivorous web), flagellates and viruses together increased viral production. Differences in the composition of the bacterial community composition explained the combined flagellate‐virus effects on viral production in the two bays.

Aerobic respiration and hypoxia in the Lower St. Lawrence Estuary: Stable isotope ratios of dissolved oxygen constrain oxygen sink partitioning - Moritz F. Lehmann; Bruce Barnett; Y. Gélinas; Denis Gilbert; Roxane J. Maranger; Alfonso Mucci; Bjorn Sundby; Benoit Thibodeau (Limnology and Oceanography, 2009)
We measured the concentration and the stable isotope ratios of dissolved oxygen in the water column in the Estuary and Gulf of St. Lawrence to determine the relative importance of pelagic and benthic dissolved oxygen respiration to the development of hypoxic deep waters. The progressive landward decrease of dissolved oxygen in the bottom waters along the axis of the Laurentian Channel (LC) is accompanied by an increase in the 18 O: 16 O ratio, as would be expected from O‐isotope fractionation associated with bacterial oxygen respiration. The apparent O‐isotope effect, ε O‐app , of 10.8% reveals that community O‐isotope fractionation is significantly smaller than if bacterial respiration occurred solely in the water column. Our observation can best be explained by a contribution of benthic O 2 consumption occurring with a strongly reduced O‐isotope effect at the scale of sediment‐water exchange (ε O‐sed ~ 7%). The value for ε O‐sed was estimated from benthic O 2 exchange simulations using a one‐dimensional diffusion‐reaction O‐isotope model. Adopting this ε O‐sed value, and given the observed community O‐isotope fractionation, we calculate that approximately two thirds of the ecosystem respiration occurs within the sediment, in reasonable agreement with direct respiration measurements. Based on the difference between dissolved oxygen concentrations in the deep waters of the Lower St. Lawrence Estuary and in the water that enters the LC at Cabot Strait, we estimate an average respiration rate of 5500 mmol O 2 m −2 yr −1 for the 100‐m‐thick layer of bottom water along the LC, 3540 mmol O 2 m −2 yr −1 of which is attributed to bacterial benthic respiration.

Nocturnal light and lunar cycle effects on diel migration of micronekton - Kelly J. Benoit-Bird; Whitlow W. L. Au; Daniel W. Wisdoma (Limnology and Oceanography, 2009)
The roles of nocturnal light and lunar phase in the diel migration of micronekton from a nearshore scattering layer were examined. Migration patterns were measured over six complete lunar cycles using moored upward‐looking echosounders while nocturnal surface irradiance was recorded. We hypothesized that animals would remain at a constant isolume at night despite changes in nocturnal illumination between nights. The scattering layer migrated closer to the surface during dark nights than during well‐lit ones. However, this movement was not enough to compensate for observed changes in light, and at night animals often remained at light levels higher than they experience at depth during the day. Light and lunar cycle were not completely coupled, allowing separation of the light and lunar phases. Contrary to the initial hypothesis, lunar phase accounted for substantially more of the variability in layer migration than surface irradiance, showing strong effects on the scattering layer’s depth and animal density within the layer. Changes in layer depth and animal density were amplified a small amount by variations in light level but were minimized by the seafloor in shallow areas. The horizontal component of the scattering layer’s migration was also affected by lunar phase, with animals remaining further offshore in deeper waters during nights near and during the full moon, even when these were not the nights with the highest light levels. These results suggest that moonlight may be a cue for an endogenous lunar rhythm in the process of diel migration rather than a direct cause.

Role of permanent host association with the Madagascar hissing-cockroach, Gromphadorhina portentosa, on the developmental water requirements of the mite, Gromphadorholaelaps schaeferi - J. A. Yoder; B. Z. Hedges; J. B. Benoit; G. D. Keeney (Journal of Comparative Physiology B, 2009)

Edge gradients provide evidence of ecological interactions in planktonic thin layers - Kelly J. Benoit-Bird; Timothy J. Cowles; Christopher E. Wingard (Limnology and Oceanography, 2009)
Physical, optical, and acoustical data from Monterey Bay, California, USA, describing the distributions of phytoplankton, zooplankton, and small fish as well as gradients in the physical habitat were used to examine the interactions between vertically compressed plankton structures (thin layers), their consumers, and the local physical forces they experience. The relationship between upper and lower edge gradients of a layer were used to define layer ‘shape'. The steepness of the vertical gradient on the top vs. the bottom of the plankton layer was correlated to the difference in the relative abundance of consumers above and below the layer. Phytoplankton layer gradients were steeper when more zooplankton were present on one side of the layer vs. the other while zooplankton layers were more diffuse when a greater number of fish were adjacent to one side of the layer than the other. Both layer types showed nearly symmetrical gradients when predators were in low abundance or absent. Predator‐associated differences in phytoplankton and zooplankton layer shape were not correlated with vertical gradients in shear or mixing potential surrounding layers. In the absence of strong physical gradients, grazers can play an important role in structuring plankton thin layers. These observations likely represent one end of a continuum of biological and physical forcing responsible for formation and maintenance of thin plankton layers.

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Influence of agricultural practices on micrometerological spatial variations at local and regional scales - D. Courault; F. Jacob; V. Benoit; M. Weiss; O. Marloie; J. F. Hanocq; E. Fillol; A. Olioso; G. Dedieu; P. Gouaux; M. Gay; A. French (International Journal of Remote Sensing, 2009)

Antarctic Collembolans Use Chemical Signals to Promote Aggregation and Egg Laying - J. B. Benoit; M. A. Elnitsky; G. G. Schulte; R. E. Lee; D. L. Denlinger (Journal of Insect Behavior, 2009)

Regulation of the external mycoflora of the giant Madagascar hissing-cockroach,gromphadorhina portentosa, by its mite associate,gromphadorholaelaps schaeferi, and its implications on human health - Jay A. Yoder; Michael J. Chambers; Michael R. Condon; Joshua B. Benoit; Lawrence W. Zettler (Symbiosis, 2009)

Molecular characterisation of a cypovirus isolated from the western spruce budworm Choristoneura occidentalis - Robert I. Graham; Benoit Morin; Renée Lapointe; Vincent G. Nealis; Christopher J. Lucarotti (Archives of Virology, 2008)

Adaptations for the maintenance of water balance by three species of Antarctic mites - J. B. Benoit; J. A. Yoder; G. Lopez-Martinez; M. A. Elnitsky; R. E. Lee; D. L. Denlinger (Polar Biology, 2008)

Biotechnological applications and potential of fungal feruloyl esterases based on prevalence, classification and biochemical diversity - Isabelle Benoit; Etienne G. J. Danchin; Robert-Jan Bleichrodt; Ronald P. de Vries (Biotechnology Letters, 2008)

Nickel-binding and accessory proteins facilitating Ni-enzyme maturation in Helicobacter pylori - Robert J. Maier; Stéphane L. Benoit; Susmitha Seshadri (BioMetals, 2007)

Selection of nitrogen‐fixing deficient Burkholderia vietnamiensis strains by cystic fibrosis patients: involvement of nif gene deletions and auxotrophic mutations - Aymeric Menard; Claire Monnez; Paulina Estrada de los Santos; Christine Segonds; Jesus Caballero‐Mellado; John J. LiPuma; Gerard Chabanon; Benoit Cournoyer (Environmental Microbiology, 2007)
Summary Burkholderia vietnamiensis is the third most prevalent species of the Burkholderia cepacia complex (Bcc) found in cystic fibrosis (CF) patients. Its ability at fixing nitrogen makes it one of the main Bcc species showing strong filiations with environmental reservoirs. In this study, 83% (29 over 35) of the B. vietnamiensis CF isolates and 100% of the environmental ones (over 29) were found expressing the dinitrogenase complex (encoded by the nif cluster) which is essential in N 2 fixation. Among the deficient strains, two were found growing with ammonium chloride suggesting that they were defective in N 2 fixation, and four with amino acids supplements suggesting that they were harbouring auxotrophic mutations. To get insights about the genetic events that led to the emergence of the N 2 ‐fixing defective strains, a genetic analysis of B. vietnamiensis nitrogen‐fixing property was undertaken. A 40‐kb‐long nif cluster and nif regulatory genes were identified within the B. vietnamiensis strain G4 genome sequence, and analysed. Transposon mutagenesis and nifH genetic marker exchanges showed the nif cluster and several other genes like gltB (encoding a subunit of the glutamate synthase) to play a key role in B. vietnamiensis ability at growing in nitrogen‐free media. nif cluster DNA probings of restricted genomic DNA blots showed a full deletion of the nif cluster for one of the N 2 ‐fixing defective strain while the other one showed a genetic organization similar to the one of the G4 strain. For 17% of B. vietnamiensis clinical strains, CF lungs appeared to have favoured the selection of mutations or deletions leading to N 2 ‐fixing deficiencies.

Habitat requirements of the seabird tick, Ixodes uriae (Acari: Ixodidae), from the Antarctic Peninsula in relation to water balance characteristics of eggs, nonfed and engorged stages - J. B. Benoit; J. A. Yoder; G. Lopez-Martinez; M. A. Elnitsky; R. E. Lee; D. L. Denlinger (Journal of Comparative Physiology B, 2007)

National campaigns to improve antibiotic use - Herman Goossens; Didier Guillemot; Matus Ferech; Benoit Schlemmer; Michiel Costers; Marije van Breda; Lee J. Baker; Otto Cars; Peter G. Davey (European Journal of Clinical Pharmacology, 2006)

Genomics of hybrid poplar ( Populus trichocarpa × deltoides ) interacting with forest tent caterpillars ( Malacosoma disstria ): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar - STEVEN RALPH; CLAIRE ODDY; DAWN COOPER; HESTHER YUEH; SHARON JANCSIK; NATALIA KOLOSOVA; RYAN N. PHILIPPE; DANA AESCHLIMAN; RICK WHITE; DEZENE HUBER; CAROL E. RITLAND; FRANÇOIS BENOIT; et al. (Molecular Ecology, 2006)
As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar ( Populus spp.) ESTs by focusing on herbivore‐ and elicitor‐treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 standard, normalized or full‐length cDNA libraries, we generated 139 007 3′‐ or 5′‐end sequenced ESTs, representing more than one‐third of the c. 385 000 publicly available Populus ESTs. Clustering and assembly of 107 519 3′‐end ESTs resulted in 14 451 contigs and 20 560 singletons, altogether representing 35 011 putative unique transcripts, or potentially more than three‐quarters of the predicted c. 45 000 genes in the poplar genome. Using this EST resource, we developed a cDNA microarray containing 15 496 unique genes, which was utilized to monitor gene expression in poplar leaves in response to herbivory by forest tent caterpillars ( Malacosoma disstria ). After 24 h of feeding, 1191 genes were classified as up‐regulated, compared to only 537 down‐regulated. Functional classification of this induced gene set revealed genes with roles in plant defence (e.g. endochitinases, Kunitz protease inhibitors), octadecanoid and ethylene signalling (e.g. lipoxygenase, allene oxide synthase, 1‐aminocyclopropane‐1‐carboxylate oxidase), transport (e.g. ABC proteins, calreticulin), secondary metabolism [e.g. polyphenol oxidase, isoflavone reductase, (–)‐germacrene D synthase] and transcriptional regulation [e.g. leucine‐rich repeat transmembrane kinase, several transcription factor classes (zinc finger C3H type, AP2/EREBP, WRKY, bHLH)]. This study provides the first genome‐scale approach to characterize insect‐induced defences in a woody perennial providing a solid platform for functional investigation of plant–insect interactions in poplar.

Lithospheric controls on the formation of provinces hosting giant orogenic gold deposits - Frank P. Bierlein; David I. Groves; Richard J. Goldfarb; Benoit Dubé (Mineralium Deposita, 2006)

A high blood lactate induced by heavy exercise does not affect the increase in submaximal $$\dot V{\text{O}}_2 $$ with hyperoxia - F. B. Favier; F. Prieur; O. Grataloup; T. Busso; J. Castells; C. Denis; A. Geyssant; H. Benoit (European Journal of Applied Physiology, 2005)

DUSKY DOLPHIN ( LAGENORHYNCHUS OBSCURUS ) FORAGING IN TWO DIFFERENT HABITATS: ACTIVE ACOUSTIC DETECTION OF DOLPHINS AND THEIR PREY - Kelly J. Benoit‐Bird; Bernd Würsig; Cynthia J. Mfadden (Marine Mammal Science, 2004)
A bstract Active‐acoustic surveys were used to determine the distribution of dusky dolphins and potential prey in two different New Zealand locations. During seven survey days off Kaikoura Canyon, dusky dolphins were found within the DeepScattering Layer (DSL) at 2000 when it rose to within 125 m of the surface. As the DSL rose to 30 m at 0100, the observed depth of dolphins decreased, presumably as the dolphins followed the vertical migration of their prey. Acoustically identified subgroups of coordinated animals ranged from one to five dolphins. Time, depth of layer, and layer variance contributed significantly to predicting foraging dusky dolphin subgroup size. In the much shallower and more enclosed Admiralty Bay, dolphins noted at the surface as foraging were always detected with the sonar, but were never observed in coordinated subgroups during the brief (two‐day) study there. In Admiralty Bay dolphin abundance was correlated with mean volume scattering from potential prey in the water column; and when volume scattering, an index of prey density, was low, dolphins were rarely present. Ecological differences between the deep waters of Kaikoura Canyon and the shallow nearshore waters of Admiralty Bay may result in differences in how, when, and in what social groupings dusky dolphins forage.

Prey dynamics affect foraging by a pelagic predator (Stenella longirostris) over a range of spatial and temporal scales - Kelly J. Benoit-Bird; Whitlow W. L. Au (Behavioral Ecology and Sociobiology, 2003)

Framework for modelling data uncertainty in life cycle inventories - Mark A. J. Huijbregts; Gregory Norris; Rolf Bretz; Andreas Ciroth; Benoit Maurice; Bo von Bahr; Bo Weidema; Angeline S. H. de Beaufort (The International Journal of Life Cycle Assessment, 2001)

MICA Sequences 2000 - James Robinson; Martha Pérez-Rodríguez; Matthew J. Waller; Benoit Cuillerier; Seiamak Bahram; Zhu Yao; Ekkehard D. Albert; J. Alejandro Madrigal; Steven G. E. Marsh (Immunogenetics, 2001)

Low-Substrate Regulated Microaerophilic Behavior as a Stress Response of Aquatic and Soil Bacteria - Raja Mazumder; Holly C. Pinkart; Patrick S. Alban; Tommy J. Phelps; Robert E. Benoit (Current Microbiology, 2000)

A Simulation Tool for Industrial Ecology: Creating a Board Game - Benoit Cushman‐Roisin; Norman J. Rice III; Michael A. Moldaver (Journal of Industrial Ecology, 1999)
Summary This article presents a board game that was developed for use as a simulation tool in teaching the basic concepts of industrial ecology (IE). The game, with the automobile industry as its theme, includes realistic numbers and displays a variety of IE principles. The objectives of the simulation, however, transcend the automobile industry and apply to other manufacturing industries. They include: pollution prevention, design for environment (in several forms, including design for disassembly), environmental management, and life‐cycle assessment. The game has already been played by engineering and business professors, graduate students in environmental engineering, government representatives, and industry executives. A statistical analysis performed on pre‐ and post‐game questionnaires indicates that the game is an effective teaching tool.

A system to simulate gas exchange in humans to control quality of metabolic measurements - F. Prieur; T. Busso; J. Castells; R. Bonnefoy; H. Benoit; A. Geyssant; C. Denis (European Journal of Applied Physiology, 1998)

Physical Aging of Progesterone-Loaded Poly(D,L,-lactide-co-glycolide) Microspheres - V. Rosilio; M. Deyme; J. P. Benoit; G. Madelmont (Pharmaceutical Research, 1998)

Accuracy of pulse oximetry during intense exercise under severe hypoxic conditions - H. Benoit; F. Costes; L. Feasson; J. R. Lacour; F. Roche; C. Denis; A. Geyssant; J. C. Barthlmy (European Journal of Applied Physiology, 1997)

Effects of fertilizer on insecticides adsorption and biodegradation in crop soils - J. Rouchaud; A. Thirion; A. Wauters; F. Van de Steene; F. Benoit; N. Ceustermans; J. Gillet; S. Marchand; L. Vanparys (Archives of Environmental Contamination and Toxicology, 1996)

Influence of cow manure and composts on the effects of chlorfenvinphos on field crops - J. Rouchaud; F. Gustin; F. Benoit; N. Ceustermans; J. Gillet; F. Van de Steene; C. Pelerents (Archives of Environmental Contamination and Toxicology, 1992)

Excess and deficient water stress effects on 30 years of Aroostook County potato yields - G. R. Benoit; W. J. Grant (American Journal of Potato Research, 1985)

Potato top growth as influenced by temperatures - G. R. Benoit; C. D. Stanley; W. J. Grant; D. B. Torrey (American Journal of Potato Research, 1983)

Plant water deficit effects on Aroostook County potato yields over 30 years 1 - G. R. Benoit; W. J. Grant (American Journal of Potato Research, 1980)

Choix de l'hôte et comportement trophique des larves deTrichogramma evanescens [Hym.: Trichogrammatidae] en fonction du développement embryonnaire deEphestia kuehniella etOstrinia nubilalis [Lep.: Pyralidae] - M. Benoit; J. Voegelé (BioControl, 1979)